Optical laminate and organic el display device including the same
By using protective films of specific thickness and material on both sides of the circular polarizer and controlling the dimensional deformation rate of each layer, the problems of forward bending and bubble generation are solved, and the display quality of the display device is improved.
Patent Information
- Application Number
- JP2023123585
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-28
- Publication Date
- 2025-02-07
AI Technical Summary
In the prior art, circular polarizers are prone to positive curls in high temperature and high humidity environments, causing air to enter the display device, resulting in small bubbles, and affecting the display effect.
By using protective films of specific thickness and material on both sides of the circular polarizer and controlling the dimensional deformation rate of each layer, it is ensured that the dimensional deformation rate between each layer meets a specific relationship and preventing forward bending and bubble generation.
It effectively suppresses the occurrence of forward bending, reduces the generation of air bubbles, and improves the display quality of the display device.
Smart Images

Figure 2025019777000007 
Figure 2025019777000001 
Figure 2025019777000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an optical laminate and a display device including the optical laminate. [Background technology]
[0002] A circular polarizing plate is an optical member in which a polarizing plate and a retardation plate are laminated, and is used, for example, in devices that display images, such as organic EL image display devices, to cut reflected light from electrodes that constitute the device and improve visibility. Conventionally, circular polarizing plates have been widely used in which a retardation plate is laminated via a pressure-sensitive adhesive layer on a polarizing plate in which a polarizer protective film is laminated on both sides of a polarizer, and an optical laminate in which a pressure-sensitive adhesive layer is provided on the retardation plate side in order to laminate such a circular polarizing plate on a display element is known (for example, Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2022-96970 Summary of the Invention [Problem to be solved by the invention]
[0004] As the polarizer protective film to be disposed on both sides of the polarizer, films having different constituent materials and thicknesses may be used in combination from the viewpoint of desired functions and ease of handling. In such an optical laminate in which different polarizer protective films are laminated on both sides of a polarizer, the retardation plate side may become convex and warp over time, i.e., a so-called positive curl may occur significantly, even in an environment maintained at a relatively constant temperature and humidity, such as a clean room environment. In such an optical laminate with positive curl, air is easily entrained when the laminate is attached to a display element, and minute air bubbles are likely to occur at the end of the laminate, which may lead to display defects in an image display device.
[0005] An object of the present invention is to provide an optical laminate that can suppress the occurrence of positive curl over time and can suppress the inclusion of minute air bubbles at the ends of the optical laminate when it is attached to a display element. [Means for solving the problem]
[0006] The present inventors have conducted extensive research to solve the above problems and have completed the present invention. [1] An optical laminate comprising a first polarizer protective film, a first adhesive layer, a polyvinyl alcohol-based polarizing film, a second adhesive layer, a second polarizer protective film, a first adhesive layer, and a retardation film made of a polymer of a polymerizable liquid crystal compound, which are adjacent to each other in this order, and a third protective film laminated on the first polarizer protective film side via a second adhesive layer, The thickness of the retardation film is 0.5 to 10 μm, After 48 hours have elapsed in an environment having a temperature of 40° C. and a relative humidity of 60%, the dimensional deformation rate (H1) of the first polarizer protective film, the dimensional deformation rate (H2) of the second polarizer protective film, and the dimensional deformation rate (H3) of the third protective film are expressed by the following formulas (1) and (2): -0.300 ≦ H1-H2 ≦ -0.001 (1) -0.040 ≦ (H3+H1)-H2 ≦0.100 (2) An optical laminate that satisfies the above requirements. [2] The thickness (T2) of the second polarizer protective film and the thickness (T3) of the third protective film are expressed by the following formula (3): 45 ≦ (T3 / T2)×100 ≦350 (3) The optical laminate according to the above [1], [3] The optical laminate according to the above [1] or [2], wherein the third protective film has a thickness of 10 to 100 μm. [4] The optical laminate according to any one of the above [1] to [3], further comprising a cured resin layer on the opposite side of the third protective film from the circular polarizing plate side. [5] The optical laminate according to any one of the above [1] to [4], wherein the third protective film is a triacetyl cellulose film or a polymethyl methacrylate polymer film. [6] The optical laminate according to any one of [1] to [5] above, wherein a peeling force required for peeling the third protective film from the optical laminate is 1 N / 25 mm or more. [7] An organic electroluminescence display device comprising the optical laminate described in [1] above. Effect of the Invention
[0007] According to the present invention, it is possible to provide an optical laminate that can suppress the occurrence of positive curl over time and can suppress the inclusion of minute air bubbles at the ends of the optical laminate when it is attached to a display element. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of a layer structure of an optical laminate of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, the embodiments of the present invention will be described in detail. Note that the scope of the present invention is not limited to the embodiments described here, and various modifications can be made without departing from the spirit of the present invention.
[0010] <Optical laminate> As shown in FIG. 1, the optical laminate 13 of the present invention includes a circular polarizer 12 in which a polarizer 11 including a first polarizer protective film 1, a first adhesive layer 2, a polyvinyl alcohol-based polarizing film 3, a second adhesive layer 4, and a second polarizer protective film 5 is laminated adjacent to the first adhesive layer 6 and a retardation film 7 including a polymer of a polymerizable liquid crystal compound in this order. Furthermore, the circular polarizer 12 has a third protective film 9 on the first polarizer protective film 1 side via a second adhesive layer 8. The second adhesive layer and the third protective film are usually adjacent to each other. The optical laminate of the present invention includes a third protective film in addition to the first polarizer protective film and the second polarizer protective film provided on both sides of the polyvinyl alcohol-based polarizing film (hereinafter, also simply referred to as "polarizing film") to protect the polarizing film, and the generation of warping over time of the optical laminate can be suppressed by controlling the dimensional deformation rate of these three protective films. When the optical laminate of the present invention is incorporated into an image display device or the like, the third protective film 9 is usually not peeled off from the optical laminate 13, but is incorporated into the image display device or the like as one of the components of the optical laminate 13. For example, a front panel or the like can be laminated onto the surface of the third protective film opposite to the first adhesive layer via a pressure-sensitive adhesive layer.
[0011] The optical laminate of the present invention may include other layers for constituting the optical laminate in addition to the first polarizer protective film (hereinafter also referred to as "first protective film"), the first adhesive layer, the polarizing film, the second adhesive layer, the second polarizer protective film (hereinafter also referred to as "second protective film"), the first adhesive layer, the retardation film (hereinafter simply referred to as "retardation film") composed of a polymer of a polymerizable liquid crystal compound, the second adhesive layer, and the third protective film, as long as the effects of the present invention are not affected. The other layers are layers that can be laminated, for example, on the outside of the third protective film (the opposite side to the second adhesive layer) and / or the outside of the retardation film (the opposite side to the first adhesive layer), and examples thereof include a cured resin layer (such as a hard coat layer) for protecting the polarizing film or the optical laminate, an optical compensation layer, a second retardation layer, an additional (adhesive) adhesive layer other than the first (adhesive) adhesive layer and the second (adhesive) adhesive layer, a base layer, and the like.
[0012] In the present invention, when the dimensional deformation rate of the first protective film after 48 hours has elapsed in an environment having a temperature of 40° C. and a relative humidity of 60% is H1 and the dimensional deformation rate of the second protective film is H2, H1 and H2 satisfy the following formula (1): -0.300 ≦ H1-H2 ≦ -0.001 (1) When the dimensional change rate H1 of the first protective film and the dimensional change rate H2 of the second protective film satisfy the above formula (1), a slight difference occurs between the dimensional change rate of the first protective film and the dimensional change rate of the second protective film. If there is such a difference in the dimensional change rate of the two protective films located on both sides of the polarizing film via an adhesive layer, warping (positive curl) that makes the second protective film side convex is likely to occur. This type of warping often occurs over time, and may occur even in a relatively constant temperature and humidity environment such as a clean room. For example, if warping occurs during storage, etc., air may be entrained when the film is attached to a display element or the like during incorporation into an image display device, etc., which may cause display defects in the image display device.
[0013] Usually, the smaller the value of H1-H2 in the range of formula (1), the larger the difference in the dimensional change rate between the first protective film and the second protective film. Therefore, it is considered that the closer the value of H1-H2 is to -0.300, the more likely the configuration is to cause positive curling over time. In the present invention, as described below, by providing a third protective film that satisfies specific conditions to such a polarizing plate that is prone to cause positive curling over time, the effect of suppressing the occurrence of the positive curl is excellent. In the present invention, the value of H1-H2 may be, for example, -0.300 or more and -0.005 or less, or -0.300 or more and -0.01 or less, and when such a polarizing plate is included, the effect of the present invention may be more remarkable.
[0014] In the present invention, when the dimensional deformation rate of the third protective film after 48 hours has elapsed in an environment at a temperature of 40° C. and a relative humidity of 60% is defined as H3, H1, H2, and H3 are expressed by the following formula (2): -0.040 ≦ (H3+H1)-H2 ≦0.100 (2) As described above, a polarizing plate satisfying formula (1) is prone to positive curl over time due to the difference in the dimensional change rate of the two protective films located on both sides of the polarizing film. Formula (2) means that the total dimensional change rate (H3+H1) of the two protective films (first protective film and third protective film) laminated on one side of the polarizer is equivalent to the dimensional change rate (H2) of the second protective film laminated on the other side of the polarizer. The optical laminate of the present invention is configured so that the dimensional change rates of the protective films located on both sides of the polarizer satisfy the above relationship, and has a high effect of suppressing the occurrence of positive curl over time.
[0015] When the total dimensional change rate of the first protective film and the third protective film is equal to the dimensional change rate of the second protective film, the occurrence of positive curling over time can be effectively suppressed. This makes it possible to suppress the inclusion of minute air bubbles at the end of the optical laminate when it is attached to a display element, even after long-term storage, for example, for six months or more. The value of (H3+H1)-H2 is preferably -0.030 or more and 0.080 or less, more preferably -0.030 or more and 0.060 or less, and even more preferably -0.020 or more and 0.040 or less.
[0016] In the present invention, the dimensional change rate H1 of the first protective film is calculated according to the following formula. Dimensional change rate (H1) = (H1 48 -H10) / H1 48 ×100 (i) [In the formula, H1 48 means the dimension of the first protective film in a predetermined direction after the first protective film is left standing alone in an environment of 40°C and 60% relative humidity for 48 hours, and H10 means the initial dimension of the first protective film in the predetermined direction before being left standing in an environment of 40°C and 60% RH for 48 hours.
[0017] Here, in the present invention, the initial dimension (H10) of the first protective film refers to the dimension of the first protective film, which is the subject of dimensional change calculation, when the film is left to stand for 168 hours in an environment with a temperature of 25°C and a relative humidity of 55%. By carrying out such pretreatment, it is possible to suppress the occurrence of measurement errors due to storage conditions of the laminate and protective film before measurement. In addition, H1 48 For example, when the first protective film is cut and the initial dimension (H10) in the longitudinal direction is measured, the dimension (H1 48 ) is measured and the dimensional change rate is calculated. That is, the dimensional change rate H1 is (1) The first protective film for which the dimensional change rate is to be determined is allowed to stand for 168 hours in an environment of 25°C and 55% RH, and then the dimension of the first protective film in a predetermined direction is measured as the initial dimension H10, (2) Next, the first film whose initial dimensions have been measured is left to stand for 48 hours in an environment of 40°C and 60% RH, and then the dimension H1 in the same direction as the initial dimensions is measured. 48 Measure The initial dimension H10 and dimension H1 obtained in the measurements (1) and (2) above 48 The dimensional change rate H1 is a value calculated based on the above formula (i) from the above. The dimensional change rate H1 calculated in this way may be either a positive value (i.e., elongation or expansion) or a negative value (i.e., contraction). The dimensional change rate is calculated by measuring the initial dimensions H10 in different directions of the film to be measured, storing the film under the above-mentioned specific storage conditions, and then calculating the dimensions H1 in the same direction as the directions in which the initial dimensions were measured. 48 Measure each of them, and measure the initial dimension H10 and dimension H1 in the same direction. 48 The value may be an average value calculated based on the above formula (i). The dimensions of the protective film can be measured, for example, using an image dimension measuring device such as Nikon NEXIV (VMZ-R4540).
[0018] The dimensional change rate H2 of the second protective film and the dimensional change rate H3 of the third protective film can be measured and calculated in the same manner as H1. In this case, in the measurement method and formula (i) of the dimensional change rate H1 of the first protective film, H1 is replaced with H2 or H3, H10 is replaced with H20 or H30, and H1 48 H2 48 or H3 48 Read as follows. In the present invention, a cured resin layer such as a hard coat layer or an optically functional layer capable of imparting various optical functions may be formed on the surface of each of the first to third protective films, as described below. When such a cured resin layer is formed directly on the surface of the protective film, the dimensional change rate is measured and calculated with the cured resin layer and the protective film as a whole.
[0019] In the present invention, the dimensional change rate of each protective film is not particularly limited as long as it satisfies the above formula (1) and formula (2); however, if the dimensional change rate of the protective film is large (as an absolute value), it becomes difficult to control the relationship of the dimensional change rate among the three protective films. For this reason, in one embodiment of the present invention, the dimensional change rate H1 of the first protective film may be, for example, -0.3 to 0.1, and preferably -0.2 to 0.05. The dimensional change rate H2 of the second protective film may be, for example, -0.1 to 0.3, and preferably -0.05 to 0.2. Furthermore, the dimensional change rate H3 of the third protective film may be, for example, -0.1 to 0.3, and preferably -0.05 to 0.2. In addition, when the dimensional change rate of each protective film is within the above range, it is advantageous in that the dimensional change of the entire laminate during long-term storage can be suppressed.
[0020] In one embodiment of the present invention, the absolute value of the difference between the dimensional change rate H2 of the second protective film and the dimensional change rate H3 of the third protective film is preferably 0.1 or less, preferably 0.06 or less, more preferably 0.03 or less. When the second protective film and the third protective film show similar dimensional change behavior, the effect of suppressing positive curl tends to be enhanced.
[0021] The dimensional change rate of each protective film varies depending on, for example, the type of material constituting the protective film, the thickness of the protective film, whether or not the protective film is surface-treated, moisture permeability, etc. That is, for example, the dimensional change rate of the protective film can be controlled within a desired range by appropriately selecting and combining the type of material constituting the protective film, the thickness of the protective film, whether or not the protective film is surface-treated, moisture permeability, etc. For example, when the protective film is made of a hydrophobic resin, for example, a polyolefin resin such as a chain polyolefin resin and a cyclic polyolefin resin; a polyester resin such as polyethylene terephthalate, etc., the dimensional change rate tends to show a negative value (i.e., shrinkage). On the other hand, when the protective film is made of a hydrophilic resin, for example, a cellulose resin such as triacetyl cellulose; a polymethyl methacrylate resin (PMMA), etc., the dimensional change rate tends to show a positive value (i.e., elongation or expansion). In addition, for example, when the thickness of the protective film is increased, the dimensional change rate generally tends to increase.
[0022] In the laminate of the present invention, the thickness (T2) of the second protective film and the thickness (T3) of the third protective film satisfy the following formula (3): 45 ≦ (T3 / T2)×100 ≦350 (3) It is preferable that the above formula (3) is satisfied. When T2 and T3 satisfy the formula (3), the effect of suppressing the occurrence of normal curl over time is excellent, and the effect of suppressing the inclusion of air bubbles when the film is attached to a display element or the like can be further improved. The value of (T3 / T2)×100 is more preferably 80 or more, further preferably 100 or more, and more preferably 300 or less, further preferably 250 or less, and may be, for example, 80 or more and 200 or less, or 80 or more and 190 or less.
[0023] In one embodiment of the present invention, the thickness of the third protective film is preferably 10 to 100 μm. When the thickness of the third protective film is within the above range, it is easy to control the value of (H3+H1)-H2 in formula (2) and the value of (T3 / T2)×100 in formula (3) to the desired range, and the effect of suppressing the occurrence of positive curl over time can be enhanced. It is also advantageous in that a thin optical laminate can be obtained while suppressing the occurrence of positive curl. The thickness of the third protective film is preferably 10 to 100 μm, more preferably 10 to 60 μm, even more preferably 10 to 40 μm, and particularly preferably 10 to 25 μm. The thickness of the third protective film can be measured by a laser microscope, a thickness meter, or the like, and the thickness of each layer or film constituting the optical laminate, such as the first protective film and the second protective film, can be measured in the same manner.
[0024] In one embodiment of the present invention, the thickness of the first protective film is preferably 10 to 60 μm, more preferably 20 to 50 μm, and even more preferably 25 to 40 μm. When the thickness of the first protective film is within the above range, the occurrence of positive curl over time can be effectively suppressed, and the optical laminate can be made thinner.
[0025] The first protective film is preferably thinner than the third protective film. When the first protective film is thinner than the third protective film, it is easier to balance the thickness and dimensional change rate with the second protective film located on the opposite side of the polarizer, and it is easier to control the value of (H3+H1)-H2 in formula (2). This is expected to further improve the effect of suppressing the occurrence of positive curl over time.
[0026] In one embodiment of the present invention, the thickness of the second protective film is preferably 5 to 60 μm, more preferably 20 to 50 μm, and even more preferably 20 to 40 μm. When the thickness of the second protective film is within the above range, the occurrence of positive curl over time can be effectively suppressed, and the optical laminate can be made thinner.
[0027] The thickness of the second protective film may be the same as or different from that of the first protective film, but in one embodiment of the present invention, it is preferable that the thickness of the first protective film and the thickness of the second protective film are approximately the same. The first protective film and the second protective film are approximately the same in thickness, which means that the difference in thickness between these two protective films is, for example, 15 μm or less, preferably 10 μm or less. When the first protective film and the second protective film are approximately the same in thickness, it becomes easier to balance the thickness and dimensional change rate of each protective film located on both sides of the polarizer, and it becomes easier to control the value of (H3+H1)-H2 in formula (2). This can be expected to further improve the effect of suppressing the occurrence of positive curl over time.
[0028] Each component of the optical layered body of the present invention will be described in detail below.
[0029] (Protective film) The first protective film, the second protective film, and the third protective film (hereinafter, when simply described as "protective film", all of the first protective film, the second protective film, and the third protective film are included) may be, for example, a resin film or the like conventionally known in the field of optical films, and the material of each protective film may be appropriately selected so as to satisfy the above formula (1) and formula (2). Examples of the resin constituting the protective film include linear or cyclic polyolefin resins such as polyethylene, polypropylene, and norbornene-based polymers; cellulose-based resins such as triacetyl cellulose, diacetyl cellulose, and cellulose acetate propionate; polyvinyl alcohol; polyester-based resins such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate; (meth)acrylic resins selected from polymethyl methacrylate resins; polycarbonate; polysulfone; polyether sulfone; polyether ketone; polyphenylene sulfide, polyphenylene oxide, and the like. Among them, from the viewpoint of strength and permeability, a resin selected from cyclic polyolefin resins, cellulose resins, and (meth)acrylic resins is preferred. These may be used alone or in combination of two or more. Such resins can be formed into a resin film by known means such as solvent casting and melt extrusion. As the protective film, a cyclic polyolefin resin film, a cellulose resin film, or an acrylic resin film is preferred.
[0030] Cyclic polyolefin resin is a general term for resins that are usually polymerized with cyclic olefins as polymerization units.Specific examples include ring-opening (co)polymers of cyclic olefins, addition polymers of cyclic olefins, copolymers (typically random copolymers) of chain olefins such as ethylene and propylene with cyclic olefins, graft polymers modified with unsaturated carboxylic acids or their derivatives, and hydrogenated products thereof.Among them, norbornene resins using norbornene monomers such as norbornene or polycyclic norbornene monomers as cyclic olefins are preferably used.
[0031] Commercially available cyclic olefin resin films can also be used. Commercially available cyclic olefin resin films include "S-Cina" (registered trademark), "SCA40" (registered trademark) (both manufactured by Sekisui Chemical Co., Ltd.), "ZEONOR Film" (registered trademark) (manufactured by Optes Co., Ltd.), and "ARTON Film" (registered trademark) (manufactured by JSR Corporation).
[0032] The cellulose resin is preferably a cellulose ester resin, and is usually an ester of cellulose and a fatty acid. Specific examples of the cellulose ester resin include triacetyl cellulose, diacetyl cellulose, cellulose tripropionate, and cellulose dipropionate. In addition, copolymers of these resins and resins in which a part of the hydroxyl groups is modified with other substituents can also be used. Among these, triacetyl cellulose (TAC) is preferred.
[0033] Commercially available cellulose-based resin films can also be used. Examples of commercially available cellulose-based resin films include "FUJITAC FILM" (manufactured by FUJIFILM Corporation), "KC8UX2M", "KC8UY" and "KC4UY" (all manufactured by Konica Minolta, Inc.).
[0034] Examples of (meth)acrylic resins include homopolymers of methacrylic acid alkyl esters or acrylic acid alkyl esters, and copolymers of methacrylic acid alkyl esters and acrylic acid alkyl esters. Specific examples of methacrylic acid alkyl esters include methyl methacrylate, ethyl methacrylate, and propyl methacrylate, and specific examples of acrylic acid alkyl esters include methyl acrylate, ethyl acrylate, and propyl acrylate. As these (meth)acrylic resins, those commercially available as general-purpose (meth)acrylic resins can be used. As the (meth)acrylic resins, those which are polymers of monofunctional acrylic monomers and have a glass transition temperature of preferably 25°C or less, more preferably 0°C or less, are further preferred. As such (meth)acrylic resins, for example, polymethyl methacrylate can be mentioned.
[0035] In one embodiment of the present invention, it is preferable to use a resin film composed of a resin whose dimensional change rate H1 does not change or tends to show a negative value (i.e., shrinkage) as the first protective film. Examples of such resin films include polyolefin-based resin films and polyester-based resin films. Among them, cyclic polyolefin-based resin films are preferable.
[0036] In one embodiment of the present invention, it is preferable to use a resin film composed of a resin whose dimensional change rate H2 tends to be a positive value (i.e., elongation or expansion) as the second protective film. Examples of such resin films include cellulose-based resin films and (meth)acrylic resin films. Among them, cellulose-based resin films are preferable, and triacetyl cellulose films are particularly preferable.
[0037] In one embodiment of the present invention, it is preferable to use a resin film composed of a resin whose dimensional change rate H3 tends to be a positive value (i.e., elongation or expansion) as the third protective film. Examples of such resin films include cellulose-based resin films and (meth)acrylic resin films. Among them, cellulose-based resin films or (meth)acrylic resin films are preferable, and triacetyl cellulose films or polymethyl methacrylate polymer films are preferable.
[0038] In the present invention, the combination of the first protective film, the second protective film, and the third protective film can be appropriately determined so that the dimensional change rate of each protective film satisfies the above formula (1) and formula (2). The first protective film, the second protective film, and the third protective film may be the same or different from each other. When the first protective film is a resin film formed from a resin different from that of the second protective film and / or the third protective film, the effect of suppressing the positive curl can be obtained even though the film is originally configured to easily cause positive curl, and the effect of the present invention tends to be remarkable. Furthermore, from the viewpoint of easy curl control, it is preferable that the first protective film or the second protective film and the third protective film are films formed from the same resin.
[0039] Examples of combinations that can be expected to easily control the dimensional change rate of each protective film to the relationship expressed by formula (1) and formula (2) and to suppress the occurrence of positive curl over time include the following combinations. Note that the combinations shown below are in the lamination order of third protective film / first protective film / second protective film. Cellulose-based resin film / cyclic polyolefin-based resin film (hereinafter, COP) / cellulose-based resin film, (meth)acrylic resin film / COP / cellulose-based resin film, more preferably, triacetyl cellulose film (hereinafter, TAC) / COP / TAC, polymethyl methacrylate resin (hereinafter, PMMA) / COP / TAC.
[0040] In order to impart adhesion to the surface of the protective film, the film surface may be modified by corona treatment, plasma treatment, frame treatment, etc., depending on the configuration of adjacent layers, etc. In addition, hard coat treatment, antireflection treatment, antistatic treatment, etc. may be performed.
[0041] In the present invention, the third protective film is usually incorporated into an image display device or the like as one of the components of the optical laminate without being peeled off from the optical laminate. For example, a protective film provided to temporarily protect a polarizing plate or the like before the optical laminate is incorporated into a display device is finally laminated so as to be peelable from the optical laminate. In such a peelably laminated film, it may be difficult to ensure sufficient support force to suppress deformation (positive curl) of the optical laminate in relation to the first protective film and the second protective film. Therefore, it is preferable that the third protective film is laminated with a certain level of adhesion force or more via the second adhesive layer so as not to peel off from other members such as the polarizing plate constituting the optical laminate. In one embodiment of the present invention, the peel force when peeling the protective film from the optical laminate is preferably 1N / 25mm or more. The upper limit is not particularly limited, and it may be firmly attached to such an extent that material destruction, i.e., destruction of the optical laminate, the third protective film, or the second adhesive layer occurs when attempting to peel it off. When the peel strength of the third protective film is equal to or greater than the lower limit, peeling from the optical laminate can be suppressed, and the third protective film can function sufficiently to prevent positive curl.
[0042] The peel strength of the third protective film is a value measured as a peel strength required to peel the third protective film to be measured from the layer to which the third protective film is bonded via the second adhesive layer (for example, the first protective film in FIG. 1) of the optical laminate to be measured. For example, in a test piece in which the surface of the optical laminate to be measured opposite the third protective film to be measured from the first adhesive layer of the retardation film is bonded to a glass plate with an adhesive, the peel strength is measured as a peel strength required to peel the third protective film to be measured from the optical laminate of the test piece. When the third protective film is peeled, the peel surface may be between the third protective film and the second adhesive layer, or between the layer to which the third protective film is bonded via the second adhesive layer and the second adhesive layer. The peel strength can be measured according to the 90° peel test method specified in JIS K 6854-1:1999.
[0043] The peel strength of the third protective film can be controlled, for example, by the type and thickness of the third protective film, the surface treatment state, the configuration and thickness of the layer laminated between the third protective film and the second adhesive layer, the surface treatment state, the type and thickness of the second adhesive layer, etc.
[0044] The third protective film located on the viewing side when incorporated into a display device or the like may function for image display (display screen or the like) (for example, function to improve the visibility of images), and may have optical functions such as a retardation function (quarter-wave plate or the like), a brightness improvement function, an anti-glare function, an anti-reflection function, a diffusion function, a light collection function, etc. In this case, the third protective film itself may be a single layer having such optical functions, or may have a multilayer structure in which an optically functional layer having various optical functions is formed on the resin film as described above.
[0045] In one embodiment of the present invention, the optical laminate of the present invention preferably further comprises a cured resin layer on the side opposite to the circularly polarizing plate of the third protective film from the viewpoint of preventing surface scratches and obtaining a function of adjusting the dimensional change rate. The cured resin layer may be, for example, a hard coat layer located on the outermost layer of the optical laminate for protecting and strengthening the optical laminate, or may be a layer having the above-mentioned various optical functions (for example, an anti-glare layer or an anti-reflection layer). When the optical laminate includes the cured resin layer, the thickness of the cured resin layer is preferably 0.5 to 10 μm, more preferably 1 to 5 μm, and even more preferably 2 μm to 5 μm. When the thickness of the cured resin layer is within the above range, the desired function of the cured resin layer can be exhibited without affecting the function that the third protective film can fulfill in the present invention, and the dimensional change of the third protective film can be adjusted, so that accurate curl control in the present invention can be easily achieved.
[0046] (Polyvinyl alcohol polarizing film) The polyvinyl alcohol-based polarizing film constituting the optical laminate of the present invention is a film having a polarizing function.This polarizing film is typically a stretched film that adsorbs a dichroic dye having absorption anisotropy, and can be produced, for example, through a process of uniaxially stretching a polyvinyl alcohol-based resin film, a process of dyeing the polyvinyl alcohol-based resin film with a dichroic dye to adsorb the dichroic dye, a process of treating the polyvinyl alcohol-based resin film that adsorbs the dichroic dye with a boric acid aqueous solution, and a process of washing with water after the process with the boric acid aqueous solution.
[0047] Polyvinyl alcohol resins are obtained by saponifying polyvinyl acetate resins. Examples of polyvinyl acetate resins include polyvinyl acetate, which is a homopolymer of vinyl acetate, and copolymers of vinyl acetate and other monomers copolymerizable therewith. Examples of other monomers copolymerizable with vinyl acetate include unsaturated carboxylic acids, olefins, vinyl ethers, unsaturated sulfonic acids, and acrylamides having an ammonium group.
[0048] The degree of saponification of the polyvinyl alcohol resin is usually about 85 to 100 mol%, preferably 90 mol% or more, more preferably 98 mol% or more. The polyvinyl alcohol resin may be a partially modified polyvinyl alcohol, for example, polyvinyl formal or polyvinyl acetal modified with aldehydes can also be used. The degree of polymerization of the polyvinyl alcohol resin is usually about 1,000 to 10,000, preferably in the range of 1,500 to 5,000.
[0049] Such a polyvinyl alcohol-based resin is used as a raw film for a polarizing film. The method for forming a film of the polyvinyl alcohol-based resin is not particularly limited, and the film can be formed by a known method. The thickness of the polyvinyl alcohol-based raw film can be, for example, about 10 to 150 μm.
[0050] The uniaxial stretching of the polyvinyl alcohol-based resin film may be performed before dyeing with a dichroic dye, or may be performed simultaneously with or after dyeing. When the uniaxial stretching is performed after dyeing, the uniaxial stretching may be performed before or during the boric acid treatment. It is also possible to perform the uniaxial stretching at these multiple stages. In the uniaxial stretching, the film may be uniaxially stretched between rolls having different peripheral speeds, or may be uniaxially stretched using a heated roll. The uniaxial stretching may be dry stretching in which the film is stretched in the air, or wet stretching in which the polyvinyl alcohol-based resin film is stretched in a swollen state using a solvent. The stretching ratio is usually about 3 to 8 times.
[0051] Dyeing of a polyvinyl alcohol-based resin film with a dichroic dye is carried out, for example, by a method of immersing the polyvinyl alcohol-based resin film in an aqueous solution containing the dichroic dye.
[0052] Specifically, iodine or a dichroic organic dye is used as the dichroic pigment. Examples of the dichroic organic dye include a dichroic direct dye made of a disazo compound such as CIDIRECT RED 39, and a dichroic direct dye made of a compound such as trisazo or tetrakisazo. It is preferable that the polyvinyl alcohol resin film is immersed in water before the dyeing process.
[0053] When iodine is used as the dichroic dye, a method of dyeing a polyvinyl alcohol resin film by immersing it in an aqueous solution containing iodine and potassium iodide is usually adopted. The content of iodine in this aqueous solution is usually about 0.01 to 1 part by mass per 100 parts by mass of water. The content of potassium iodide is usually about 0.5 to 20 parts by mass per 100 parts by mass of water. The temperature of the aqueous solution used for dyeing is usually about 20 to 40°C. The immersion time in this aqueous solution (dyeing time) is usually about 20 to 1,800 seconds.
[0054] On the other hand, when a dichroic organic dye is used as the dichroic pigment, a method of dyeing a polyvinyl alcohol resin film by immersing it in an aqueous solution containing a water-soluble dichroic dye is usually adopted. The content of the dichroic organic dye in this aqueous solution is usually 1×10 -4 ~10 parts by mass, preferably 1 × 10 -3 ~1 part by mass, more preferably 1 × 10 -3 ~1×10 -2 The amount of the dye in the aqueous solution is expressed by parts by mass. This aqueous solution may contain an inorganic salt such as sodium sulfate as a dyeing assistant. The temperature of the aqueous dichroic dye solution used for dyeing is usually about 20 to 80° C. The immersion time in the aqueous solution (dyeing time) is usually about 10 to 1,800 seconds.
[0055] The boric acid treatment after dyeing with a dichroic dye can usually be carried out by immersing the dyed polyvinyl alcohol resin film in an aqueous boric acid solution. The content of boric acid in this aqueous boric acid solution is usually about 2 to 15 parts by mass, preferably 5 to 12 parts by mass, per 100 parts by mass of water. When iodine is used as the dichroic dye, this aqueous boric acid solution preferably contains potassium iodide, and in this case, the content of potassium iodide is usually about 0.1 to 15 parts by mass, preferably 5 to 12 parts by mass, per 100 parts by mass of water. The immersion time in the aqueous boric acid solution is usually about 60 to 1,200 seconds, preferably 150 to 600 seconds, and more preferably 200 to 400 seconds. The temperature of the boric acid treatment is usually 50°C or higher, preferably 50 to 85°C, and more preferably 60 to 80°C.
[0056] The polyvinyl alcohol-based resin film after the boric acid treatment is usually washed with water. The washing can be performed, for example, by immersing the boric acid-treated polyvinyl alcohol-based resin film in water. The temperature of the water used in the washing is usually about 5 to 40° C. The immersion time is usually about 1 to 120 seconds.
[0057] After washing with water, the film is dried to obtain a polarizer. The drying can be performed using, for example, a hot air dryer or a far-infrared heater. The temperature for the drying is usually about 30 to 100°C, and preferably 50 to 80°C. The time for the drying is usually about 60 to 600 seconds, and preferably 120 to 600 seconds. The moisture content of the polarizing film is reduced to a practical level by the drying. The moisture content is usually about 5 to 20 mass%, and preferably 8 to 15 mass%. When the moisture content is within the above range, a polarizing film having appropriate flexibility and excellent thermal stability can be obtained.
[0058] In the present invention, the thickness of the polarizing film is preferably from 5 to 40 μm, more preferably from 5 to 30 μm, further preferably from 5 to 20 μm, and particularly preferably from 5 to 15 μm.
[0059] (First adhesive layer and second adhesive layer) In the optical laminate of the present invention, a first protective film is laminated on one side of a polarizing film via a first adhesive layer, and a second protective film is laminated on the other side of the polarizing film via a second adhesive layer. These layers are laminated adjacent to each other to form a laminate that functions as a polarizing plate. The first adhesive layer and the second adhesive layer (hereinafter, when simply described as "adhesive layer", the first adhesive layer and the second adhesive layer are the objects) are layers formed from an adhesive. The adhesive layer can be formed from a known adhesive as long as it can function as a layer that bonds a polarizing film and a protective film. As such an adhesive, a conventionally known adhesive can be used without particular restrictions, and can be appropriately selected according to the type of protective film to be bonded, and the properties and applications required for the optical laminate. Examples of adhesives that can form the first adhesive layer and the second adhesive layer include active energy ray curing adhesives, water-based adhesives, organic solvent-based adhesives, and solventless adhesives. Among them, water-based adhesives or active energy ray curing adhesives are preferred.
[0060] Aqueous adhesives generally have a composition that uses, for example, a polyvinyl alcohol resin or a urethane resin as the main component and, in order to improve adhesion, contains a crosslinking agent or a curing compound such as an isocyanate compound or an epoxy compound.
[0061] When a polyvinyl alcohol resin is used as the main component of the aqueous adhesive, modified polyvinyl alcohol resins such as partially saponified polyvinyl alcohol and fully saponified polyvinyl alcohol, carboxyl group-modified polyvinyl alcohol, acetoacetyl group-modified polyvinyl alcohol, methylol group-modified polyvinyl alcohol, and amino group-modified polyvinyl alcohol may be used. An aqueous solution of such a polyvinyl alcohol resin is used as the aqueous adhesive. The concentration of the polyvinyl alcohol resin in the aqueous adhesive is usually 1 to 10 parts by mass, preferably 1 to 5 parts by mass, based on 100 parts by mass of water.
[0062] In order to improve adhesion, the aqueous adhesive consisting of an aqueous solution of polyvinyl alcohol resin can be blended with a curing compound such as a polyhydric aldehyde, a water-soluble epoxy resin, a melamine compound, a zirconia compound, or a zinc compound. An example of a water-soluble epoxy resin is a water-soluble polyamide epoxy resin obtained by reacting epichlorohydrin with a polyamide polyamine obtained by reacting a polyalkylene polyamine such as diethylenetriamine or triethylenetetramine with a dicarboxylic acid such as adipic acid. Examples of commercially available products of such polyamide epoxy resins include "Sumirez Resin 650" and "Sumirez Resin 675" sold by Sumika Chemtex Co., Ltd., and "WS-525" sold by Nippon PMC Co., Ltd. When a water-soluble epoxy resin is blended, the amount of the resin added is usually about 1 to 100 parts by mass, preferably 1 to 50 parts by mass, based on 100 parts by mass of the polyvinyl alcohol resin.
[0063] In addition, when a urethane resin is used as the main component of the water-based adhesive, it is effective to use a polyester ionomer urethane resin as the main component of the water-based adhesive. The polyester ionomer urethane resin referred to here is a urethane resin having a polyester skeleton, into which a small amount of an ionic component (hydrophilic component) has been introduced. Such an ionomer urethane resin can be emulsified directly in water without using an emulsifier to form an emulsion, and therefore can be used as a water-based adhesive. When using a polyester ionomer urethane resin, it is effective to add a water-soluble epoxy compound as a crosslinking agent.
[0064] These components constituting the water-based adhesive are usually used in a state dissolved in water. The water-based adhesive is applied to the surface on which the adhesive layer is to be formed and dried to obtain the adhesive layer. The components that do not dissolve in water may be in a state dispersed in the system.
[0065] A method for forming an adhesive layer on a polarizing film from a water-based adhesive includes a method of directly applying the above-mentioned adhesive composition to the surface of the polarizing film and drying it. The thickness of the adhesive layer is usually about 0.001 to 5 μm, preferably 0.01 μm or more, and preferably 2 μm or less, and more preferably 1 μm or less. When the adhesive layer is within the above range, the positive curl suppression effect obtained by controlling the dimensional change rate of each protective film and the necessary adhesiveness can be ensured without affecting the optical properties and / or appearance of the polarizing plate.
[0066] The active energy ray curable adhesive is an adhesive that cures when irradiated with active energy rays such as ultraviolet rays. Examples of the active energy ray curable adhesive include a cationic polymerizable adhesive containing an epoxy compound and a cationic polymerization initiator, a radical polymerizable adhesive containing an acrylic curing component and a radical polymerization initiator, an adhesive containing both a cationic polymerizable curing component such as an epoxy compound and a radical polymerizable curing component such as an acrylic compound, and further containing a cationic polymerization initiator and a radical polymerization initiator, and an adhesive that does not contain these polymerization initiators and is cured by irradiation with an electron beam.
[0067] Among them, a radically polymerizable active energy ray curable adhesive containing an acrylic curing component and a photoradical polymerization initiator, and a cationic polymerizable active energy ray curable adhesive containing an epoxy compound and a photocationic polymerization initiator are preferred. Examples of the acrylic curing component include (meth)acrylates such as methyl (meth)acrylate and hydroxyethyl (meth)acrylate, and (meth)acrylic acid. The active energy ray curable adhesive containing an epoxy compound may further contain a compound other than the epoxy compound. Examples of the compound other than the epoxy compound include an oxetane compound and an acrylic compound.
[0068] As the photoradical polymerization initiator and the cationic polymerization initiator, initiators known in the field of active energy ray curable adhesives can be appropriately selected and used. The content of the photoradical polymerization initiator and the cationic polymerization initiator is usually 0.5 to 20 parts by mass, preferably 1 to 15 parts by mass, based on 100 parts by mass of the active energy ray curable adhesive.
[0069] A method for forming an adhesive layer on a polarizing film from an active energy ray curable adhesive includes a method of applying the above-mentioned adhesive composition to the surface of a polarizing film, drying the solvent as necessary, and then irradiating with active energy rays to form an adhesive layer. The thickness of the adhesive layer is usually about 0.001 to 5 μm, preferably 0.01 μm or more, and preferably 2 μm or less, and more preferably 1 μm or less. When the adhesive layer is within the above range, the positive curl suppression effect obtained by controlling the dimensional change rate of each protective film and the required adhesiveness can be ensured without affecting the optical properties and / or appearance of the polarizing plate.
[0070] In the optical laminate of the present invention, the first adhesive layer and the second adhesive layer may be the same or different in composition, thickness, and the like.
[0071] (First adhesive layer and second adhesive layer) In the optical laminate of the present invention, a retardation film is laminated on the surface of the second protective film opposite to the polarizing film via a first adhesive layer. The layers from the first protective film to the retardation film are laminated adjacent to each other to form a laminate that functions as a circular polarizing plate. In addition, a third protective film is laminated on the first protective film side of the circular polarizing plate via a second adhesive layer. The first adhesive layer and the second adhesive layer (hereinafter, when simply described as "adhesive layer", the first adhesive layer and the second adhesive layer are the objects) are layers formed from an adhesive (meaning a pressure-sensitive adhesive, an adhesive, or an agent having both of these properties). The adhesive layer can be formed from a known adhesive as long as it can function as a layer that bonds the third protective film and the circular polarizing plate, and the second protective film and the retardation film. As such an adhesive, a conventionally known adhesive can be used without any particular restrictions, and can be appropriately selected according to the type of protective film or retardation film to be bonded, the properties required for the optical laminate, and the use.
[0072] Examples of adhesives capable of forming the first adhesive layer and the second adhesive layer include the adhesives described above as being capable of forming the first adhesive layer, etc., and adhesives mainly composed of resins such as (meth)acrylic, rubber, urethane, ester, silicone, and polyvinyl ether. The adhesive may be an active energy ray curable adhesive, a heat curable adhesive, etc. The adhesives forming the first adhesive layer and the second adhesive layer are preferably adhesives, and among them, adhesives having a (meth)acrylic resin as a base polymer, which is excellent in transparency, weather resistance, heat resistance, etc., are preferred.
[0073] The (meth)acrylic resin (base polymer) used in the adhesive may be, for example, a polymer or copolymer containing one or more (meth)acrylic acid esters as monomer components, such as butyl (meth)acrylate, methyl (meth)acrylate, ethyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, lauryl (meth)acrylate, isooctyl (meth)acrylate, isodecyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and isobornyl (meth)acrylate. The (meth)acrylic resin may also be a copolymer of a polar monomer. Examples of polar monomers include monomers having a carboxylic acid group, a carboxyl group, a hydroxyl group, an amide group, an amino group, an epoxy group, and the like, such as (meth)acrylic acid, 2-hydroxypropyl (meth)acrylate, hydroxyethyl (meth)acrylate, (meth)acrylamide, N,N-dimethylaminoethyl (meth)acrylate, and glycidyl (meth)acrylate.
[0074] In one embodiment of the present invention, the structural unit derived from a (meth)acrylic acid ester in the (meth)acrylic resin constituting the pressure-sensitive adhesive is preferably 80 to 100 mass%, more preferably 85 mass% or more, and even more preferably 90 mass% or more, based on the total mass of all structural units constituting the (meth)acrylic resin. In addition, when the (meth)acrylic resin contains a structural unit derived from a polar monomer, the structural unit derived from the polar monomer is preferably 0.1 to 10 mass%, more preferably 0.5 mass% or more, even more preferably 1 mass% or more, and more preferably 8 mass% or less, based on the total mass of all structural units constituting the (meth)acrylic resin.
[0075] The weight average molecular weight (hereinafter, simply referred to as "Mw") of the (meth)acrylic resin is preferably 500,000 to 2,500,000. When the weight average molecular weight is 500,000 or more, the durability of the first adhesive layer can be improved in a high temperature and high humidity environment. When the weight average molecular weight is 2,500,000 or less, the operability during application of the adhesive is improved. The molecular weight distribution (Mw / Mn), which is expressed as the ratio of the weight average molecular weight (Mw) to the number average molecular weight (hereinafter, simply referred to as "Mn"), is usually 2 to 10. In this specification, the weight average molecular weight and the number average molecular weight are polystyrene equivalent values measured by gel permeation chromatography (GPC).
[0076] The adhesive may contain only the acrylic resin, but may also contain a crosslinking agent. Examples of crosslinking agents include divalent or higher metal ions that form carboxylate metal salts with carboxyl groups; polyamine compounds that form amide bonds with carboxyl groups; polyepoxy compounds or polyols that form ester bonds with carboxyl groups; and polyisocyanate compounds that form amide bonds with carboxyl groups. Among these, polyisocyanate compounds are preferred from the viewpoints of crosslinking speed, durability, etc.
[0077] When a crosslinking agent is contained, the proportion thereof is, for example, 0.01 to 10 parts by mass, preferably 0.1 to 3 parts by mass, and more preferably 0.1 to 1 part by mass, relative to 100 parts by mass of the base polymer.
[0078] The adhesive may further contain a silane compound as necessary. By containing a silane compound, the adhesive layer formed from the adhesive can have high adhesion to the layer to be laminated. Examples of the silane compound include vinyltrimethoxysilane, vinyltriethoxysilane, vinyltris(2-methoxyethoxy)silane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylethoxydimethylsilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-chloropropylmethyldimethoxysilane, 3-chloropropyltrimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, and 3-mercaptopropyltrimethoxysilane. These may be used alone or in combination of two or more.
[0079] When a silane compound is contained, the content thereof in the adhesive is usually 0.01 to 10 parts by mass, preferably 0.03 to 5 parts by mass, more preferably 0.05 to 2 parts by mass, and even more preferably 0.1 to 1 part by mass, per 100 parts by mass of the base polymer.
[0080] In this specification, the active energy ray curable pressure-sensitive adhesive means a pressure-sensitive adhesive that has the property of being cured by irradiation with active energy rays such as ultraviolet rays or electron beams, that has adhesiveness even before irradiation with active energy rays and can be adhered to an adherend such as a film, and that has the property of being cured by irradiation with active energy rays and capable of adjusting adhesion, etc. The active energy ray curable pressure-sensitive adhesive is preferably an ultraviolet ray curable pressure-sensitive adhesive.
[0081] The active energy ray curable pressure sensitive adhesive generally comprises an energy ray polymerizable compound in addition to a base polymer such as the (meth)acrylic resin and a crosslinking agent as described above. If necessary, it may further comprise a photopolymerization initiator, a photosensitizer, etc.
[0082] Examples of the active energy ray polymerizable compound include (meth)acrylic compounds such as (meth)acrylate monomers having at least one (meth)acryloyloxy group in the molecule; and (meth)acryloyloxy group-containing compounds such as (meth)acrylate oligomers obtained by reacting two or more types of functional group-containing compounds and having at least two (meth)acryloyloxy groups in the molecule.
[0083] The adhesive may further contain components that are conventionally used as components constituting an adhesive, such as resins other than the base polymer, tackifiers, fillers (metal powders and other inorganic powders, etc.), antioxidants, UV absorbers, dyes, pigments, colorants, defoamers, and corrosion inhibitors.
[0084] In one embodiment of the present invention, the first adhesive layer and the second adhesive layer may be composed of a reaction product of an adhesive containing a base polymer such as the (meth)acrylic resin, a crosslinking agent and a silane compound as described above. Such an adhesive layer can be formed by applying, for example, an organic solvent diluted solution of an adhesive containing the above components to a surface on which the adhesive layer is to be formed, and drying the solution.
[0085] In one embodiment of the present invention, the first adhesive layer and the second adhesive layer may be layers formed from an active energy ray curable adhesive. When the adhesive layer is formed from an active energy ray curable adhesive, for example, an organic solvent dilution of the adhesive comprising the above-mentioned components is applied to the surface on which the adhesive layer is to be formed, and the adhesive layer is dried to form a cured product layer having a desired degree of curing by irradiating the adhesive layer with active energy rays.
[0086] The first adhesive layer and the second adhesive layer may be the same or different in composition, thickness, configuration, and the like.
[0087] The thickness of the first adhesive layer can be appropriately determined depending on the composition of the adhesive, the configuration and size of the optical laminate, etc. In one embodiment of the present invention, the thickness of the first adhesive layer is usually 1 to 30 μm, preferably 5 to 25 μm, and more preferably 5 to 20 μm. When the thickness of the first adhesive layer is within the above range, the retardation film can be bonded with high adhesion, and a thin laminate structure having an excellent effect of suppressing the occurrence of positive curl over time can be formed.
[0088] The thickness of the second adhesive layer can be appropriately determined depending on the composition of the adhesive, the configuration and size of the optical laminate, etc. In one embodiment of the present invention, the thickness of the second adhesive layer is preferably 1 to 50 μm, more preferably 3 to 25 μm, and further preferably 5 to 15 μm. When the thickness of the second adhesive layer is within the above range, the third protective film can be attached to the first protective film side of the polarizing plate with high adhesion, and a laminate structure excellent in the effect of suppressing the occurrence of positive curl over time can be formed.
[0089] The water vapor permeability of each of the first adhesive layer and the second adhesive layer at a temperature of 40° C. and a relative humidity of 90% is preferably 1,000 to 10,000 g / m 2 24h, preferably 2,000~9,000g / m 2 When the water vapor transmission rate of the adhesive layer is within the above range, deformation is unlikely to occur even in a high temperature and high humidity environment, and the effect of suppressing the occurrence of positive curl over time can be improved. The water vapor transmission rate of the adhesive layer can be controlled within a desired range by the composition, thickness, etc. of the adhesive forming the adhesive layer. The water vapor permeability of the pressure-sensitive adhesive layer can be measured using a water vapor permeability measuring device. When it is difficult to measure the water vapor permeability of the pressure-sensitive adhesive layer alone, the pressure-sensitive adhesive may be attached to a substrate having high moisture permeability, and the water vapor permeability may be calculated from the ratio to the substrate having high moisture permeability.
[0090] In the optical laminate of the present invention, the storage modulus of the first adhesive layer and the second adhesive layer is preferably 0.01 MPa or more, more preferably 0.05 MPa or more, particularly preferably 0.07 MPa or more, and is preferably 0.5 MPa or less, more preferably 0.2 MPa or less, particularly preferably 0.15 MPa or less. When the storage modulus of the adhesive layer is within the above range, the layers bonded via the adhesive layer are less likely to slip, and the effect of suppressing the occurrence of positive curl can be improved. The storage modulus of the adhesive layer can be controlled to a desired range by the composition of the adhesive forming the adhesive layer. In the adhesive layer formed from an active energy ray curable adhesive, the storage modulus can often be increased. The storage modulus of the adhesive layer can be measured using a viscoelasticity measuring device. In detail, it can be measured by, for example, the method described in the examples described later.
[0091] The glass transition temperature (Tg) of the first adhesive layer and the second adhesive layer is preferably not higher than room temperature (25° C.), more preferably not higher than 0° C., and usually not lower than −40° C. When the glass transition temperature of the adhesive layer is within the above range, sufficient adhesive strength can be exhibited. The glass transition temperature of the adhesive layer can be controlled to a desired range by the type and amount of the base polymer, etc. contained in the adhesive forming the adhesive layer, the type and amount of the monomer used to form the polymer, the combination, etc. The glass transition temperature of the adhesive layer can be measured, for example, by the method described in the examples described below.
[0092] (phase contrast film) In the optical laminate of the present invention, the retardation film laminated adjacent to the first adhesive layer is composed of a polymer of a polymerizable liquid crystal compound. When the retardation film laminated to the polarizing plate via the first adhesive layer is a cured layer (cured film) of a polymerizable liquid crystal compound, a thinner circular polarizing plate can be formed compared to when the layer having retardation is made of a stretched film, but the retardation film is thin (for example, 5 μm or less), and therefore positive curling is likely to occur over time. In the optical laminate of the present invention, a third protective film is provided on the surface of the circular polarizing plate opposite the retardation film, and the dimensional change rate of the third film is controlled in relation to the first protective film and the second protective film, thereby effectively suppressing the occurrence of positive curling that is inherently likely to occur when a thin retardation film is used.
[0093] From the viewpoint that the above-mentioned effect is easily remarkable, in one embodiment of the present invention, the thickness of the retardation film laminated adjacent to the first pressure-sensitive adhesive layer is 0.5 to 5 μm, preferably 0.5 to 3.0 μm, more preferably 1.0 to 3.0 μm. In the present invention, the retardation film is a film that shows retardation in the in-plane or thickness direction, and may be a layer made of a polymer of a polymerizable liquid crystal compound alone, or may be made of the layer made of the polymer and an alignment film for forming the layer when the layer is adjacent to the alignment film. When the retardation film includes an alignment film, a thickness of 0.1 μm to 5 μm is further added.
[0094] In this specification, the retardation film may be one or two or more. When two or more retardation films are included, the thickness of each retardation film can be appropriately determined according to the optical properties required for each retardation film, the configuration and use of the optical laminate, etc., and the thicknesses may be the same or different from each other. Hereinafter, when the optical laminate includes two or more retardation films, a laminate of multiple retardation films via an adhesive layer may be called a composite retardation film. The composite retardation film, that is, the total thickness of two or more retardation films and the adhesive layer interposed therebetween, is preferably 15 μm or less, more preferably 10 μm or less, even more preferably 8 μm or less, and particularly preferably 6 μm or less.
[0095] In order that the optical laminate of the present invention can function as a circular polarizing plate, the optical laminate has the following formula (4): 120nm≦Re(550)≦170nm (4) (wherein Re(λ) represents the in-plane retardation value of the retardation film at a wavelength of λ nm) It is preferable that the optical laminate of the present invention contains only one retardation film, and that the retardation film satisfies the above formula (4). When the in-plane retardation Re(550) of the retardation film is within the range of formula (4), the retardation film functions as a quarter-wave plate, and the effect of improving the front reflection hue (the effect of suppressing coloring) is easily enhanced when an optical laminate (circular polarizing plate) including the retardation film is applied to an organic EL display device, etc. A more preferable range of the in-plane retardation value is 130 nm≦Re(550)≦150 nm.
[0096] In addition to the formula (4), the retardation film may be represented by the following formulas (5) and (6): Re(450) / Re(550)≦1.00 (5) 1.00≦Re(650) / Re(550) (6) (wherein Re(λ) represents the in-plane retardation value of the retardation film at a wavelength of λ nm) It is preferable that the retardation film satisfies the formula (5) and the formula (6), the retardation film shows a so-called reverse wavelength dispersion, in which the in-plane retardation value at a short wavelength is smaller than the in-plane retardation value at a long wavelength. An optical laminate (circular polarizing plate) having such a retardation film tends to have excellent front hue when incorporated into an organic EL display device or the like. From the viewpoint of improving the reverse wavelength dispersion and further enhancing the effect of improving the reflected hue in the front direction, Re(450) / Re(550) is preferably 0.70 or more, more preferably 0.78 or more, and also preferably 0.92 or less, more preferably 0.90 or less, even more preferably 0.87 or less, particularly preferably 0.86 or less, and even more particularly preferably 0.85 or less. In addition, Re(650) / Re(550) is preferably 1.01 or more, more preferably 1.02 or more.
[0097] The in-plane retardation value can be adjusted by the film thickness dA of the retardation film. The in-plane retardation value is determined by the formula ReA(λ) = (nxA(λ) - nyA(λ)) × dA [where nxA(λ) represents the principal refractive index at a wavelength of λ nm in the plane of the retardation film, nyA(λ) represents the refractive index at a wavelength of λ nm in the direction orthogonal to the direction of nxA in the same plane as nxA, and dA indicates the film thickness of the retardation film]. Therefore, in order to obtain a desired in-plane retardation value (ReA(λ): the in-plane retardation value of the retardation film at a wavelength of λ (nm)), it is only necessary to adjust the three-dimensional refractive index and the film thickness dA.
[0098] The optical laminate of the present invention preferably includes a retardation film composed of a "horizontally aligned liquid crystal cured film" in which the polymerizable liquid crystal compound is cured in a state of being horizontally aligned with respect to the plane of the retardation film. When the optical laminate of the present invention includes only one retardation film, usually, the retardation film is a "horizontally aligned liquid crystal cured film", and preferably satisfies the above formulas (4) to (6).
[0099] In addition to the retardation film having a quarter-wave plate function, the optical laminate of the present invention may further include a retardation film that is a positive C-plate (nx ≒ ny < nz). The retardation film that is a positive C-plate is a "vertically aligned liquid crystal cured film" in which the polymerizable liquid crystal compound is cured in a state of being vertically aligned with respect to the plane of the retardation film. By including a combination of a retardation film having a quarter-wave plate function and a retardation film that is a positive C-plate, when the optical laminate is applied to an organic EL display device or the like, it is possible to expect an improvement in the oblique reflection hue in addition to an improvement in the front reflection hue.
[0100] When the optical laminate of the present invention includes a retardation film that is a positive C-plate, it is preferable that the retardation film (hereinafter also referred to as "vertically aligned liquid crystal cured film") satisfies the formulas (7) to (9). Rth(450) / Rth(550) ≦ 1.00 (7) 1.00 ≦ Rth(650) / Rth(550) (8) -100 nm ≦ Rth(550) ≦ -40 nm (9) (In the formula, Rth(λ) represents a retardation value in the thickness direction of the vertically aligned liquid crystal cured film at a wavelength of λ nm, and RthC=((nxC(λ)+nyC(λ)) / 2-nzC)×dC (In the formula, dC represents a thickness of the vertically aligned liquid crystal cured film, nxC represents a principal refractive index at a wavelength of λ nm in a direction parallel to the plane of the vertically aligned liquid crystal cured film in an index ellipsoid formed by the vertically aligned liquid crystal cured film, nyC represents a refractive index at a wavelength of λ nm in a direction parallel to the plane of the vertically aligned liquid crystal cured film and perpendicular to the direction of nxC in an index ellipsoid formed by the vertically aligned liquid crystal cured film, and nzC represents a refractive index at a wavelength of λ nm in a direction perpendicular to the plane of the vertically aligned liquid crystal cured film in an index ellipsoid formed by the vertically aligned liquid crystal cured film).)
[0101] When the vertically aligned liquid crystal cured film satisfies the formulas (7) and (8), in a circular polarizing plate including the retardation film (vertically aligned liquid crystal cured film), the decrease in ellipticity can be suppressed on the short wavelength side, and the oblique reflection hue can be improved. The value of Rth(450) / Rth(550) in the vertically aligned liquid crystal cured film is preferably 0.70 or more, more preferably 0.78 or more, and also preferably 0.92 or less, more preferably 0.90 or less, even more preferably 0.87 or less, particularly preferably 0.86 or less, and even more particularly preferably 0.85 or less. In addition, Rth(650) / Rth(550) is preferably 1.01 or more, more preferably 1.02 or more.
[0102] In addition, when the retardation film, which is a positive C plate, satisfies formula (9), the oblique reflection hue can be improved when an optical laminate (circular polarizing plate) including the retardation film is applied to an organic EL display device. The retardation value Rth(550) in the thickness direction of the retardation film (vertically aligned liquid crystal cured film) is more preferably -90 nm or more, further preferably -80 nm or more, and more preferably -50 nm or less.
[0103] The optical laminate of the present invention may further include a retardation film having a 1 / 2 wavelength plate function in addition to the retardation film having a 1 / 4 wavelength plate function. In this case, the retardation film functioning as the 1 / 4 wavelength plate may satisfy the following formulas (10), (12), and (13). In addition, the retardation film functioning as the 1 / 2 wavelength plate may satisfy the following formulas (11), (12), and (13). 100nm <Re(550)<160nm (10) 200nm <Re(550)<320nm (11) Re(450) / Re(550)≧1.00 (12) 1.00≧Re(650) / Re(550) (13)
[0104] By stacking such a retardation film having a quarter-wave plate function and a retardation film having a half-wave plate function so that their slow axes intersect at approximately 60 degrees, it can function as a quarter-wave plate over a wide range (broadband) spanning almost the entire visible light range.
[0105] Examples of a method for obtaining a composite retardation film including a retardation film having a 1 / 2 wavelength plate function in addition to a retardation film having a 1 / 4 wavelength plate function include the methods described in JP2015-163935A and WO2013 / 137464A. From the viewpoint of viewing angle compensation to provide the same appearance from an oblique direction as when viewed from the front, preferably, the retardation film having the 1 / 2 wavelength plate function is a retardation film formed from a discotic liquid crystal compound, and the retardation film having the 1 / 4 wavelength plate function is a retardation film formed from a rod-shaped liquid crystal compound.
[0106] The above-mentioned retardation film having a quarter-wave plate function, the retardation film functioning as a positive C layer, and the retardation film having a half-wave plate function may each be tilt-oriented, cholesteric-oriented, or nematic-oriented.
[0107] The polymerizable liquid crystal compound capable of forming the retardation film in the present invention can be appropriately selected from the polymerizable liquid crystal compounds conventionally known in the field of retardation films according to the desired optical properties. The polymerizable liquid crystal compounds usable in the present invention can be classified into rod-shaped type (rod-shaped liquid crystal compound) and discotic type (discotic liquid crystal compound, discotic liquid crystal compound) based on their shape, and any liquid crystal compound can be used. Furthermore, two or more rod-shaped liquid crystal compounds, two or more discotic liquid crystal compounds, or a mixture of rod-shaped liquid crystal compounds and discotic liquid crystal compounds may be used.
[0108] The polymerizable liquid crystal compound is a liquid crystal compound having a polymerizable group. In general, the polymer (cured product) obtained by polymerizing the polymerizable liquid crystal compound alone in a state of being aligned in a specific direction includes a polymerizable liquid crystal compound exhibiting positive wavelength dispersion and a polymerizable liquid crystal compound exhibiting reverse wavelength dispersion. In the present invention, only one type of polymerizable liquid crystal compound may be used, or both types of polymerizable liquid crystal compounds may be mixed and used. In addition, when the optical laminate includes a retardation film having a quarter-wave plate function and a retardation film made of a liquid crystal cured film that is a positive C plate, the polymerizable liquid crystal compounds constituting them may be the same as or different from each other. For example, if the retardation film having a quarter-wave plate function and / or the retardation film made of a liquid crystal cured film that is a positive C plate are each a cured film of a polymerizable liquid crystal composition containing a polymerizable liquid crystal compound exhibiting so-called reverse wavelength dispersion, the optical properties of the optical laminate are likely to be improved.
[0109] In the present invention, the polymerizable group of the polymerizable liquid crystal compound forming the retardation film is preferably a photopolymerizable group. The photopolymerizable group is a polymerizable group that can participate in a polymerization reaction by a reactive species generated from a photopolymerization initiator, such as an active radical or an acid. Examples of the photopolymerizable group include a vinyl group, a vinyloxy group, a 1-chlorovinyl group, an isopropenyl group, a 4-vinylphenyl group, a (meth)acryloyl group, an oxiranyl group, and an oxetanyl group. Among them, a (meth)acryloyl group, a vinyloxy group, an oxiranyl group, and an oxetanyl group are preferred, and an acryloyl group is more preferred.
[0110] The liquid crystallinity exhibited by the polymerizable liquid crystal compound may be thermotropic liquid crystal or lyotropic liquid crystal, but thermotropic liquid crystal is preferred in terms of the ability to precisely control the film thickness. The phase ordered structure in the thermotropic liquid crystal may be nematic liquid crystal, smectic liquid crystal, or discotic liquid crystal. The polymerizable liquid crystal compound may be used alone or in combination of two or more kinds.
[0111] In the present invention, the retardation film may be configured to include an alignment film. The alignment film has an alignment regulating force that aligns the polymerizable liquid crystal compound in a desired direction, and a precisely aligned retardation film can be easily obtained by applying a polymerizable liquid crystal composition onto the alignment film. The alignment film preferably has solvent resistance that does not dissolve the polymerizable liquid crystal composition by application, and also has heat resistance in a heat treatment for removing the solvent or orienting the polymerizable liquid crystal compound. Examples of the alignment film include an alignment film containing an alignment polymer, a photoalignment film, a groove alignment film having a concave-convex pattern or a plurality of grooves on the surface, and a stretched film stretched in the alignment direction. These various alignment films can be appropriately selected from those conventionally known in the field according to the desired alignment regulating force.
[0112] In one embodiment of the present invention, the horizontal alignment film having the alignment regulating force for aligning the polymerizable liquid crystal compound in the horizontal direction is preferably a photo-alignment film from the viewpoints of the accuracy of the alignment angle and the quality. The photo-alignment film is also advantageous in that the direction of the alignment regulating force can be arbitrarily controlled by selecting the polarization direction of the irradiated polarized light.
[0113] A photo-alignment film is usually obtained by applying a composition containing a polymer, oligomer or monomer having a photoreactive group and a solvent (hereinafter also referred to as a "photo-alignment film-forming composition") onto a substrate or the like, and irradiating it with polarized light (preferably polarized UV). When the polymer or the like contained in the photo-alignment film-forming composition has the same reactive group (e.g., a (meth)acryloyl group) as the functional group of the polymerizable group of the polymerizable liquid crystal compound forming the retardation film, the adhesion between the cured layer of the polymerizable liquid crystal compound and the alignment film tends to be improved.
[0114] The photoreactive group refers to a group that generates liquid crystal alignment ability by irradiation with light. Specifically, it includes groups involved in photoreactions that induce molecular alignment or are the origin of liquid crystal alignment ability, such as isomerization reaction, dimerization reaction, photocrosslinking reaction, or photodecomposition reaction, caused by irradiation with light. Among them, groups involved in dimerization reaction or photocrosslinking reaction are preferred in terms of excellent alignment ability. As the photoreactive group, a group having an unsaturated bond, particularly a double bond, is preferred, and a group having at least one selected from the group consisting of a carbon-carbon double bond (C=C bond), a carbon-nitrogen double bond (C=N bond), a nitrogen-nitrogen double bond (N=N bond), and a carbon-oxygen double bond (C=O bond) is particularly preferred.
[0115] In order to impart an orientation control force to the orientation film, a rubbing treatment can be performed as necessary (rubbing method). A method for imparting an orientation control force by the rubbing method includes a method in which an orientation polymer composition is applied to a substrate and annealed to bring an orientation polymer film formed on the substrate surface into contact with a rotating rubbing roll wrapped with a rubbing cloth. If masking is performed during the rubbing treatment, multiple regions (patterns) with different orientation directions can also be formed on the orientation film.
[0116] When the optical laminate of the present invention includes a composite retardation film as a retardation film, the retardation films included in the optical laminate may be laminated via a pressure-sensitive adhesive layer, or a retardation film composed of a polymer of a polymerizable liquid crystal compound may be laminated on another retardation film with or without an alignment film. For example, when a retardation film having a 1 / 4 wavelength plate function and a retardation film made of a liquid crystal cured film that is a positive C plate are included, these retardation films may be laminated via a pressure-sensitive adhesive layer, or a retardation film made of a liquid crystal cured film that is a positive C plate may be laminated on a retardation film having a 1 / 4 wavelength plate function with or without an alignment film that has a vertical alignment regulating force, or a retardation film having a 1 / 4 wavelength plate function may be laminated on a retardation film made of a liquid crystal cured film that is a positive C plate with or without an alignment film that has a horizontal alignment regulating force. When the optical laminate includes two or more different retardation films on the surface opposite to the polarizing film of the first pressure-sensitive adhesive layer, the lamination order is not particularly limited. For example, a retardation film having a quarter-wave plate function may be adjacent to the first adhesive layer, or a retardation film made of a liquid crystal cured film that is a positive C plate or a retardation film having a half-wave plate function may be adjacent to the first adhesive layer. As the adhesive for bonding a plurality of retardation films, the adhesives described as the adhesives for forming the first and second adhesive layers can be used.
[0117] When a retardation film having a quarter-wave plate function is laminated on a polarizing plate, it is preferable to laminate the retardation film so that the slow axis (optical axis) of the retardation film and the absorption axis of the polarizing film are substantially at 45°. By laminating the retardation film so that the slow axis (optical axis) of the retardation film and the absorption axis of the polarizing film are substantially at 45°, the function of a circular polarizing plate can be obtained. Note that substantially 45° is usually in the range of 45±5°.
[0118] The optical laminate of the present invention can be produced by forming and laminating the third protective film, the second adhesive layer, the first protective film, the first adhesive layer, the polarizing film, the second adhesive layer, the second protective film, the first adhesive layer, and the retardation film in an appropriate order according to the production method described above for each layer so as to have a desired configuration depending on the application, etc. For example, a polarizing plate is prepared by laminating a first protective film on one side of a polarizing film and a second protective film on the other side via an adhesive layer. Separately from this, a retardation film formed on a substrate via an alignment film is prepared, and the polarizing plate and the retardation film are bonded with a tacky adhesive to prepare a circular polarizing plate. Next, a third protective film is laminated on the first protective film side of the circular polarizing plate via a tacky adhesive to obtain an optical laminate consisting of the third protective film / second tacky adhesive layer / first protective film / first adhesive layer / polarizing film / second adhesive layer / second protective film / first tacky adhesive layer / retardation film as shown in FIG. 1. Furthermore, a cured resin layer is formed on the surface of the third protective film opposite to the second tacky adhesive layer to obtain an optical laminate consisting of the cured resin layer / third protective film / second tacky adhesive layer / first protective film / first adhesive layer / polarizing film / second adhesive layer / second protective film / first tacky adhesive layer / retardation film. Furthermore, by laminating a further retardation film to the circular polarizing plate via a pressure-sensitive adhesive, an optical laminate consisting of, for example, third protective film / second pressure-sensitive adhesive layer / first protective film / first adhesive layer / polarizing film / second adhesive layer / second protective film / first pressure-sensitive adhesive layer / retardation film / pressure-sensitive adhesive layer / retardation film can be obtained.
[0119] The optical laminate of the present invention is unlikely to curl over time, and can suppress the inclusion of minute air bubbles at the end of the optical laminate when incorporated into a display element, so that high optical performance can be expected. Therefore, the optical laminate of the present invention is suitable as a component of various display devices. In addition, since it can be stored for a long period of time, the disposal of the optical laminate due to changes over time can be reduced. A display device is a device having a display element, and includes a light-emitting element or a light-emitting device as a light source. Examples of display devices include liquid crystal display devices, organic electroluminescence (EL) display devices, inorganic electroluminescence (EL) display devices, touch panel display devices, electron emission display devices (e.g., field emission displays (FEDs) and surface field emission displays (SEDs)), electronic paper (display devices using electronic ink or electrophoretic elements, plasma display devices, projection display devices (e.g., grating light valve (GLV) display devices and displays having a digital micromirror device (DMD)), and piezoelectric ceramic displays. Liquid crystal display devices include transmissive liquid crystal display devices, semi-transmissive liquid crystal display devices, reflective liquid crystal display devices, direct-current display devices, and the like. The optical laminate of the present invention includes both a viewing type liquid crystal display device and a projection type liquid crystal display device. These display devices may be display devices that display two-dimensional images, or stereoscopic display devices that display three-dimensional images. In particular, the optical laminate of the present invention can be suitably used in organic electroluminescence (EL) display devices and inorganic electroluminescence (EL) display devices, and can also be suitably used in liquid crystal display devices and touch panel display devices. These display devices can exhibit good image display characteristics by including the optical laminate of the present invention, which has an excellent effect of suppressing the inclusion of minute air bubbles at the end of the optical laminate when incorporated into a display element. EXAMPLES
[0120] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples. In the examples and comparative examples, "%" and "parts" are "mass %" and "parts by mass" unless otherwise specified.
[0121] 1. Preparation of Polarizing Plates (1) Preparation of polarizing film A 20 μm thick polyvinyl alcohol resin film (average polymerization degree about 2400, saponification degree 99.9 mol% or more) was uniaxially stretched vertically by about 5 times by dry stretching, and then, while maintaining tension, was immersed in pure water at a temperature of 60° C. for 1 minute, and then immersed in an aqueous solution at a temperature of 28° C. in which the mass ratio of iodine / potassium iodide / water was 0.05 / 5 / 100 for 60 seconds. Thereafter, it was immersed in an aqueous solution at a temperature of 72° C. in which the mass ratio of potassium iodide / boric acid / water was 8.5 / 8.5 / 100 for 300 seconds. It was then washed with pure water at a temperature of 26° C. for 20 seconds, and then dried at a temperature of 65° C. to obtain a polarizer with a thickness of 8 μm in which iodine was adsorbed and aligned in the polyvinyl alcohol resin film.
[0122] (2) Preparation of Water-Based Adhesive for Forming the First Adhesive Layer and the Second Adhesive Layer A polyvinyl alcohol aqueous solution was prepared by dissolving 3 parts by mass of carboxyl-modified polyvinyl alcohol ("KL-318" manufactured by Kuraray Co., Ltd.) in 100 parts by mass of water. A water-soluble polyamide epoxy resin ("Sumirez Resin 650(30)" manufactured by Taoka Chemical Co., Ltd., solid content concentration 30% by mass) was mixed with the resulting aqueous solution in a ratio of 1.5 parts by mass per 100 parts by mass of water to obtain a water-based adhesive.
[0123] (3) Preparation of polarizing plates The aqueous adhesive obtained above was applied to one side of the polarizing film obtained above, and a protective film (1) [ZEONORFILM ZD-U manufactured by ZEON CORPORATION, thickness 23 μm, cyclic polyolefin resin film (COP film)] was laminated thereon, and the aqueous adhesive obtained above was applied to the other side of the polarizing film, and a protective film (2) [a triacetyl cellulose film (TAC film) having a thickness of 20 μm] was laminated thereon. The laminate obtained was dried at a temperature of 80° C. for 5 minutes to obtain a polarizing plate having protective films on both sides of the polarizing film via an adhesive layer. The layer structure of this polarizing plate is protective film (1) (COP film) / aqueous adhesive layer / polarizing film / aqueous adhesive layer / protective film (2) (TAC film).
[0124] (4) Measurement of dimensional change rate of protective film The protective film (1) (COP film) was cut into a rectangle of 150 mm x 50 mm size to be used as a measurement sample, and the dimensions of the long and short sides were precisely measured using a Nikon image measuring device "NEXIV (VMZ-R4540)" and were taken as the initial dimensions. The measurement sample was then kept in an oven at 40°C and 60% RH for 48 hours, after which the dimensions of the long and short sides were precisely measured in the same manner as in the measurement of the initial dimensions and were taken as the dimensions after 48 hours. The dimensional change rates of the long and short sides were calculated using the following formula, and the average value was taken as the dimensional change rate of the protective film (1). Dimensional change rate = (dimension after 48 hours - initial dimension) / (dimension after 48 hours) x 100 The dimensional change rate of the protective film (1) (COP film) was -0.01%.
[0125] The dimensional change rate of protective film (2) (TAC film) was also calculated as the average value of the long and short sides in the same manner as protective film (1). The dimensional change rate of protective film (2) (TAC film) was +0.02%.
[0126] 2. Preparation of a laminate including a pressure-sensitive adhesive layer (1) Preparation of adhesive layer (1) A reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, a dropping device, and a nitrogen inlet tube was charged with 95.0 parts of n-butyl acrylate, 4.0 parts of acrylic acid, 1.0 part of 2-hydroxyethyl acrylate, 200 parts of ethyl acetate, and 0.08 parts of 2,2'-azobisisobutyronitrile, and the air in the reaction vessel was replaced with nitrogen gas. The reaction solution was heated to 60°C while stirring under a nitrogen atmosphere, reacted for 6 hours, and then cooled to room temperature.
[0127] When the weight average molecular weight of a part of the obtained solution was measured, it was confirmed that a (meth)acrylic acid ester polymer of 1.8 million had been produced. The weight average molecular weight (Mw) of the (meth)acrylic resin is a polystyrene-equivalent weight average molecular weight measured under the following conditions using gel permeation chromatography (GPC). [Measurement conditions] GPC measuring device: Tosoh Corporation, HLC-8020 GPC columns (passed in the following order): Tosoh Corporation TSK guard column HXL-H TSK gel GMHXL (×2) TSK gel G2000HXL Measurement solvent: Tetrahydrofuran ·Measurement temperature: 40℃
[0128] 100 parts (solid content equivalent) of the (meth)acrylic acid ester polymer obtained in the above process, 1.5 parts (solid content equivalent) of trimethylolpropane-modified tolylene diisocyanate (manufactured by Tosoh Corporation, product name "Coronate (registered trademark) L") as an isocyanate-based crosslinking agent, 0.30 parts (solid content equivalent) of 3-glycidoxypropyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., product name "KBM403") as a silane coupling agent, and a UV-curable 7.5 parts (solid content equivalent) of ethoxylated isocyanuric acid triacrylate (manufactured by Shin-Nakamura Chemical Co., Ltd.: product name "A-9300") as a compound and 0.5 parts (solid content equivalent) of 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one (manufactured by BASF: Irgacure (registered trademark) 907) as a photopolymerization initiator were mixed, thoroughly stirred, and diluted with ethyl acetate to obtain a coating solution of adhesive composition (1).
[0129] The coating solution of the pressure-sensitive adhesive composition (1) obtained above was applied to the release-treated surface of a separator film (manufactured by Lintec Corporation: SP-PLR382190) with one side treated for release, using an applicator, so that the thickness after drying was 5 μm (measured with a Nikon digital micrometer "MH-15M"), and then dried at a temperature of 100° C. for 1 minute. A separator film (manufactured by Lintec Corporation: SP-PLR381031) with one side treated for release was laminated on the release-treated surface side to the side of the coating layer opposite to the side to which the separator was laminated after drying (exposed surface of the coating layer). Next, ultraviolet light (irradiation intensity 500 mW / cm 2 ) was applied to this coating layer through the separator film (SP-PLR382190) using a belt conveyor-equipped ultraviolet light irradiation device (manufactured by Fusion UV Systems, lamp D bulb used).2 , cumulative light intensity 500mJ / cm 2 ) to form a pressure-sensitive adhesive layer (1), thereby obtaining a pressure-sensitive adhesive layer (1) with a double-sided separator. The layer structure of this pressure-sensitive adhesive layer (1) with a double-sided separator was separator film (SP-PLR382190) / pressure-sensitive adhesive layer (1) / separator film (SP-PLR381031). The thickness of the pressure-sensitive adhesive layer (1) was 5 μm.
[0130] (2) Preparation of adhesive layer (2) A pressure-sensitive adhesive layer (2) with a separator on both sides was obtained in the same manner as in the preparation of the pressure-sensitive adhesive layer (2) above, except that the coating solution of the pressure-sensitive adhesive composition (2) was applied so that the thickness after drying was 15 μm. The layer structure of the pressure-sensitive adhesive layer (2) with a separator on both sides was separator film (SP-PLR382190) / pressure-sensitive adhesive layer (2) / separator film (SP-PLR381031). The thickness of the pressure-sensitive adhesive layer (2) was 15 μm.
[0131] (3) Measurement of water vapor permeability The water vapor permeability of the pressure-sensitive adhesive layers (1) and (2) prepared above was measured using a water vapor permeability tester (Lyssy's "Lyssy-L80-5000") under conditions of a temperature of 40°C and a relative humidity of 90%, and was found to be 7600 g / (m 2 -24h).
[0132] (4) Measurement of storage modulus A sample for measuring the storage modulus G' was prepared by laminating multiple sheets of the pressure-sensitive adhesive layers (1) and (2) to a thickness of 0.2 mm (measured with a Nikon digital micrometer "MH-15M") and punching out a cylinder with a diameter of 8 mm. This sample was measured by a torsional shear method using a viscoelasticity measuring device (Physica, MCR300) in accordance with JIS K7244-6 under the following conditions. [Measurement conditions] Normal Force FN:1N Distortion γ: 1% Frequency: 1Hz Temperature: 25℃ The storage modulus G' of the pressure-sensitive adhesive layers (1) and (2) was measured and found to be 125,000 Pa (0.125 MPa) at a temperature of 25°C.
[0133] (5) Measurement of glass transition temperature The glass transition temperatures of the pressure-sensitive adhesive layer (1) and the pressure-sensitive adhesive layer (2) were measured by the following procedure. First, 5 mg of the adhesive layer (1) or (2) was taken and placed in an aluminum press-lid type container, which was then pressed down and sealed to prepare a measurement sample. The container containing the measurement sample was set in a differential scanning calorimeter (DSC) ("EXSTAR-6000 DSC6220" sold by SII Nano Technology Co., Ltd.), and the temperature was lowered from 20°C to -60°C while purging with nitrogen gas. After reaching -60°C, the container was held for 1 minute, and then the temperature was raised from -60°C to 150°C at a heating rate of 10°C / min. When the temperature reached 150°C, the temperature was immediately lowered to 20°C. Then, from the DSC curve when the temperature was raised from -60°C to 150°C, the midpoint glass transition temperature specified in JIS K 7121-1987 "Method of measuring transition temperature of plastics" was obtained, and this was taken as the glass transition temperature of the adhesive layers (1) and (2) to be measured. The results were all below 25°C.
[0134] (6) Preparation of adhesive layer (3) A reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, a dropping device and a nitrogen inlet tube was charged with 97.0 parts of n-butyl acrylate, 1.0 parts of acrylic acid, 0.5 parts of 2-hydroxyethyl acrylate, 200 parts of ethyl acetate and 0.08 parts of 2,2'-azobisisobutyronitrile, and the air in the reaction vessel was replaced with nitrogen gas. The reaction solution was heated to 60°C while stirring under a nitrogen atmosphere, reacted for 6 hours, and then cooled to room temperature. The weight average molecular weight of a portion of the obtained solution was measured by the above procedure, and the production of a (meth)acrylic acid ester polymer of 1.8 million was confirmed.
[0135] 100 parts of the (meth)acrylic acid ester polymer obtained in the above process (solid content equivalent; the same applies below), 0.30 parts of trimethylolpropane-modified tolylene diisocyanate (manufactured by Tosoh Corporation, product name "Coronate (registered trademark) L") as an isocyanate-based crosslinking agent, and 0.30 parts of 3-glycidoxypropyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., product name "KBM403") as a silane coupling agent were mixed, thoroughly stirred, and diluted with ethyl acetate to obtain a coating solution of adhesive composition (3).
[0136] The coating solution of the adhesive composition (3) obtained above was applied to the release-treated surface of a separator film (manufactured by Lintec Corporation: SP-PLR382190) with one side subjected to release treatment, using an applicator, so that the thickness after drying was 25 μm (the thickness was measured with a Nikon digital micrometer "MH-15M"). After that, it was dried at a temperature of 100° C. for 1 minute, and a separator film (manufactured by Lintec Corporation: "SP-PLR381031") with one side subjected to release treatment was attached to the exposed surface of the coating layer after drying (the surface opposite to the surface on which the separator film was laminated), to obtain an adhesive layer (3) with a separator on both sides.
[0137] The storage modulus G' of the pressure-sensitive adhesive layer (3) was measured by the above procedure and was found to be 25,500 Pa (0.0255 MPa) at a temperature of 25° C. In addition, the glass transition temperature of the pressure-sensitive adhesive layer (3) was measured by the above procedure and was found to be 25° C. or lower.
[0138] 3. Preparation of a laminate including a retardation film (1) Preparation of retardation film (1) (i) Preparation of composition for forming photo-alignment film A composition for forming a photo-alignment film was obtained by mixing 2 parts of a photo-alignment material having the structure shown below with 98 parts of cyclopentanone (solvent) and stirring for 1 hour at a temperature of 80 ° C. The photo-alignment material having the structure shown below (weight average molecular weight: 50000, m:n = 50:50) was synthesized according to the method described in JP 2021-196514 A. Photoalignable materials: [ka]
[0139] (ii) Preparation of polymerizable liquid crystal composition (1) The polymerizable liquid crystal composition (1) was prepared by mixing the polymerizable liquid crystal compound (X6), polymerizable liquid crystal compound (X7), leveling agent, and photopolymerization initiator shown below, and further mixing N-methyl-2-pyrrolidone (NMP) so that the solid content concentration was 13%, and stirring at a temperature of 80 ° C. for 1 hour. The polymerizable liquid crystal compound (X6) and the polymerizable liquid crystal compound (X7) have the structures shown below. The polymerizable liquid crystal compound (X6) was prepared in the same manner as the method described in JP-A-2019-003177. The polymerizable liquid crystal compound (X7) was prepared in the same manner as the method described in JP-A-2009-173893. Polymerizable liquid crystal compound (X6): 90 parts Polymerizable liquid crystal compound (X7): 10 parts Leveling agent [BYK-361N (BM Chemie)]: 0.1 part Photopolymerization initiator [Irgacure OXE-03 (manufactured by BASF Japan Ltd.)]: 3 parts
[0140] ·Polymerizable liquid crystal compound (X6): [ka] ·Polymerizable liquid crystal compound (X7): [ka]
[0141] A solution was obtained by dissolving 1 mg of the polymerizable liquid crystal compound (X6) in 10 mL of chloroform. The obtained solution was placed in a measurement cell with an optical path length of 1 cm, and the measurement sample was set in an ultraviolet-visible spectrophotometer (Shimadzu Corporation's "UV-2450") to measure the absorption spectrum. The wavelength at which the maximum absorbance was obtained was read from the obtained absorption spectrum, and the maximum absorption wavelength λmax in the wavelength range of 300 to 400 nm was 356 nm.
[0142] (iii) Preparation of retardation film with substrate layer (1) The composition for forming a photo-alignment film obtained above was applied to a biaxially oriented polyethylene terephthalate (PET) film (Diafoil, manufactured by Mitsubishi Plastics, Inc.) using a bar coater to obtain a coating layer. The obtained coating layer was dried at a temperature of 120°C for 2 minutes, then cooled to room temperature to dry the coating layer, and then the dried coating layer was irradiated with 100mJ of polarized ultraviolet light (313nm standard) using a UV irradiation device (SPOT CURE SP-9; manufactured by Ushio Inc.) to obtain a photo-alignment film on the PET film. The thickness of the photo-alignment film measured using an ellipsometer M-220 manufactured by JASCO Corporation was 100nm.
[0143] The polymerizable liquid crystal composition (1) prepared above was applied onto the photoalignment film obtained on the PET film using a bar coater to form a coating layer. The formed coating layer was dried by heating at a temperature of 120°C for 2 minutes, and then cooled to room temperature. The dried coating layer was exposed to light at a dose of 500 mJ / cm2 under a nitrogen atmosphere using a high-pressure mercury lamp ("Uniquer VB-15201BY-A" manufactured by Ushio Inc.). 2 By irradiating the film with ultraviolet light of 365 nm (reference wavelength), a cured layer (1) of the polymerizable liquid crystal composition (1) was formed in which the polymerizable liquid crystal compound was cured in a state of being aligned in the PET film plane. The thickness of the cured layer (1) was measured using a laser microscope LEXT OLS4100 manufactured by Olympus Corporation and was 2 μm. As a result, a retardation film (1) with a substrate layer, consisting of a first substrate layer (PET film) / retardation film (1) (photo-aligned film / cured layer (1)), was obtained. Here, the thickness of the retardation film (1) consisting of the photo-aligned film (100 nm) and the cured layer (1) (2 μm) was 2.1 μm.
[0144] (2) Measurement of phase difference value The retardation film (1) side of the first retardation film (1) with the substrate layer was subjected to a corona treatment, and the first liquid crystal retardation layer side with the substrate layer was attached to an inorganic glass plate via an adhesive layer (1), and the first substrate layer (PET film) was peeled off and removed to obtain a test specimen. The layer structure of this test specimen was retardation film (1) [photo-alignment film / cured material layer (1)] / adhesive layer (1) / inorganic glass plate. The in-plane retardation value of this test specimen was measured using a "KOBRA-WR" manufactured by Oji Scientific Instruments. The in-plane retardation values for light with wavelengths of 450 nm, 550 nm, and 650 nm were calculated from Cauchy's dispersion formula obtained from the measurement results of the in-plane retardation values for light with wavelengths of 448.2 nm, 498.6 nm, 548.4 nm, 587.3 nm, 628.7 nm, and 748.6 nm. As a result, the in-plane retardation values were Re(450)=122 nm, Re(550)=140 nm, and Re(650)=144 nm, and the relationship between the in-plane retardation values at each wavelength was as follows: Re(450) / Re(550)=0.87 Re(650) / Re(550)=1.03 [In the formula, Re(450) represents an in-plane retardation value for light having a wavelength of 450 nm, Re(550) represents an in-plane retardation value for light having a wavelength of 550 nm, and Re(650) represents an in-plane retardation value for light having a wavelength of 650 nm.] The in-plane retardation value of the inorganic glass plate was 0 nm at wavelengths of 448.2 nm, 498.6 nm, 548.4 nm, 587.3 nm, 628.7 nm and 748.6 nm, and the in-plane retardation values at wavelengths of 450 nm, 550 nm and 650 nm were all 0 nm. Therefore, the in-plane retardation value of this test specimen is the in-plane retardation of the retardation film (1) (photo-alignment film and cured product layer (1)) constituting it.
[0145] (3) Preparation of retardation film (2) (i) Preparation of composition for forming vertical alignment film A mixture was obtained by mixing 2-phenoxyethyl acrylate, tetrahydrofurfuryl acrylate, dipentaerythritol triacrylate, and bis(2-vinyloxyethyl) ether in a ratio (mass ratio) of 1:1:4:5, and 4 parts by mass of "LUCIRIN TPO" manufactured by Ciba Japan Ltd. was added as a polymerization initiator to 100 parts by mass of the obtained mixture to prepare a composition for forming a vertical alignment film.
[0146] (ii) Preparation of polymerizable liquid crystal composition (2) The polymerizable liquid crystal composition (2) was prepared by mixing a photopolymerizable nematic liquid crystal compound (Merck's "RMM28B") and a solvent so that the solid content was 1 to 1.5% by mass. The solvent used was a mixed solvent of methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK), and cyclohexanone (CHN) in a mass ratio (MEK:MIBK:CHN) of 35:30:35.
[0147] (iii) Preparation of retardation film with substrate layer (2) A corona treatment was applied to the surface opposite to the release-treated side of a one-sided release-treated polyethylene terephthalate (PET) film ("FF-50" manufactured by Unitika Ltd., a supporting substrate (PET film (thickness 50 μm))), and the composition for forming a vertical alignment film prepared above was applied to this corona-treated surface using a slot die coater so that the thickness after curing would be 3 μm. The applied film was exposed to 200 mJ / cm 2 A vertical alignment film was formed on a PET film having one side treated for release by irradiation with ultraviolet light of 1000 nm.
[0148] The polymerizable liquid crystal composition (2) prepared above was applied to the vertical alignment film formed on the one-sided release-treated PET film above using a slot die coater so that the thickness after curing would be 1 μm, to obtain a coating layer. The coating layer was dried at a drying temperature of 75° C. for a drying time of 120 seconds, and then irradiated with ultraviolet light to polymerize the polymerizable liquid crystal compound and form a cured layer (2). This resulted in a retardation film (2) with a base layer consisting of a one-sided release-treated PET film / retardation film (2) (vertical alignment film / cured layer (2)). The retardation film (2) was a positive C plate.
[0149] (4) Preparation of composite retardation film (i) Preparation of active energy ray-curable composition (1) 3',4'-Epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate (product name: CEL2021P, manufactured by Daicel Corporation): 70 parts by mass Neopentyl glycol diglycidyl ether (product name: EX-211, manufactured by Nagase ChemteX Corporation): 20 parts by mass, 2-Ethylhexyl glycidyl ether (product name: EX-121, manufactured by Nagase ChemteX Corporation): 10 parts by mass, Cationic polymerization initiator (product name: CPI-100_50% solution, manufactured by San-Apro Co., Ltd.): 4.5 parts by mass (actual solid content 2.25 parts by mass), and 1,4-diethoxynaphthalene: 2 parts by mass The above ingredients were mixed to obtain an active energy ray-curable composition (1).
[0150] (ii) Preparation of composite retardation film with substrate layer The retardation film (1) with the substrate layer and the retardation film (2) with the substrate layer obtained above were laminated with the active energy ray curable composition (1) prepared above, with the retardation film (1) side and the retardation film (2) side facing each other. Next, ultraviolet light was irradiated from the substrate layer-attached retardation film (2) side to cure the active energy ray curable composition (1) to form an adhesive layer with a thickness of 2 μm, thereby obtaining a composite retardation film with a substrate layer. This composite retardation film with a substrate layer has a layer structure of a first substrate layer (PET film) / retardation film (1) (photoalignment film / cured product layer (1)) / adhesive layer (cured product layer of the active energy ray curable composition (1)) / retardation film (2) (cured product layer (2) / vertical alignment film) / second substrate layer (one-sided release-treated PET film).
[0151] 4. Preparation of optical laminate with separator (circular polarizing plate) From the polarizing plate obtained above, a rectangular shape was cut out so that the absorption axis direction was the long side, and the surface on the protective film (2) side (TAC film side) was subjected to corona treatment. Next, the first base layer (PET film) on the retardation film (1) side of the composite retardation film with base layer obtained above was peeled off to expose the photo-alignment film, and the exposed photo-alignment film was subjected to corona treatment. The surfaces subjected to the corona treatment described above, i.e., the TAC film side and the photo-alignment film side, were bonded together with the long sides aligned with each other via the pressure-sensitive adhesive layer (2) 15 μm thick obtained above.
[0152] Thereafter, the second substrate layer (one-sided release-treated PET film) of the substrate layer-attached retardation film (2) was peeled off to expose the vertical alignment film, and the exposed surface of the vertical alignment film was subjected to corona treatment, and the pressure-sensitive adhesive layer (3) exposed by peeling off one of the separators from the pressure-sensitive adhesive layer (3) with double-sided separator was attached thereon to obtain an optical laminate with a separator. This optical laminate with a separator has a layer structure of a polarizing plate (first protective film / first adhesive layer / polarizing film (polarizer) / second adhesive layer / second protective film) / pressure-sensitive adhesive layer (2) / retardation film (1) (photo-alignment film / cured product layer (1)) / cured product layer of active energy ray-curable composition (1) / retardation film (2) (cured product layer (2) / vertical alignment film) / pressure-sensitive adhesive layer (3) / separator film. In addition, the slow axis of the cured product layer (1) constituting the retardation film (1) intersected at 45 degrees in-plane with the absorption axis of the polarizer.
[0153] 5. Preparation of the third protective film (1) Preparation of clear hard coat film (i) Preparation of solution for forming cured resin layer A solution with a solids concentration of 40% by weight was prepared by mixing 50 parts by mass of an ultraviolet-curing urethane acrylate monomer (refractive index 1.51), 50 parts by mass of an ultraviolet-curing acrylate monomer (refractive index 1.51), 5 parts by mass of a benzophenone-based photopolymerization initiator, and toluene.
[0154] (ii) Preparation of clear hard coat film The solution obtained above was applied onto a long resin film and dried for 5 minutes at 120° C. Then, a curing treatment was performed by irradiating ultraviolet rays to form a clear hard coat layer (cured resin layer) with a flat surface and a thickness of about 4 μm, thereby producing a long clear hard coat film. As a resin film A clear hard coat film (1) is made of a 25 μm-thick triacetyl cellulose film. A clear hard coat film (2) was made using a 40 μm thick triacetyl cellulose film. A clear hard coat film (3) using a 60 μm thick triacetyl cellulose film, A clear hard coat film (4) was prepared by using a triacetyl cellulose film having a thickness of 80 μm. A clear hard coat film (5) made of a 60 μm thick acrylic film (polymethyl methacrylate polymer film) It was decided.
[0155] (2) Measurement of dimensional change rate A sample of 150 mm x 50 mm was cut out from the long clear hard coat film (1) thus produced. At this time, the sample was cut out so that the long side (150 mm) of the sample was at 45° with respect to the length direction of the long clear hard coat film (1). This was used as a measurement sample and set in a Nikon image measuring device "NEXIV (VMZ-R4540)" with the clear hard coat layer side facing up, and the dimensions of the long side and short side were precisely measured and defined as the initial dimensions. Next, after keeping it in an oven at 40 ° C and 60% RH for 48 hours, the dimensions of the long side and short side were precisely measured in the same manner and defined as the dimensions after 48 hours. The dimensional change rates of the long side and short side were calculated using the following formula, and the average value was defined as the dimensional change rate of the clear hard coat film (1). Dimensional change rate = (dimension after 48 hours - initial dimension) / (dimension after 48 hours) x 100
[0156] In the same manner as above, the dimensional change rate of the long side and the dimensional change rate of the short side of each of the clear hard coat films (2) to (5) were measured, and the dimensional change rate of each film was calculated from the average value. The results are shown in Table 1.
[0157] [Table 1]
[0158] <Example 1> The COP film surface of the separator-attached optical laminate and the TAC film surface of the clear hard coat film (1) were each subjected to a corona treatment, and then laminated via an adhesive layer (2). A sample was obtained by cutting the film into a size of 150 mm x 50 mm so that the optical axis of the polarizing film was 45° clockwise from the long side reference, and the optical axis of the retardation film was 45° further clockwise from the optical axis of the polarizing film, as viewed from the cured resin layer surface of the clear hard coat film (1). The optical laminate of Example 1 is composed of clear hard coat film (1) (cured resin layer / TAC film) / adhesive layer (2) / polarizing plate (protective film (1) / first adhesive layer / polarizing film / second adhesive layer / protective film (2)) / adhesive layer (2) / retardation film (1) (photoalignment film / cured product layer (1)) / cured product layer of active energy ray curable composition (1) / retardation film (2) (cured product layer (2) / vertical alignment film) / adhesive layer (3) / separator film. The peeling force when peeling off the clear hard coat film (1) in the optical laminate of Example 1 from the optical laminate is 1 N / 25 mm or more.
[0159] <Example 2> A sample was obtained in the same manner as in Example 1, except that the pressure-sensitive adhesive layer (2) for bonding the clear hard coat film (1) and the polarizing plate was changed to the pressure-sensitive adhesive layer (1). The optical laminate of Example 2 is composed of clear hard coat film (1) (cured resin layer / TAC film) / adhesive layer (1) / polarizing plate (protective film (1) / first adhesive layer / polarizing film / second adhesive layer / protective film (2)) / adhesive layer (2) / retardation film (1) (photoalignment film / cured product layer (1)) / cured product layer of active energy ray curable composition (1) / retardation film (2) (cured product layer (2) / vertical alignment film) / adhesive layer (3) / separator film. The peeling force when peeling off the clear hard coat film (1) in the optical laminate of Example 2 from the optical laminate is 1 N / 25 mm or more.
[0160] <Example 3> A sample was obtained in the same manner as in Example 2, except that the clear hard coat film (1) was changed to the clear hard coat film (2). The optical laminate of Example 3 is composed of clear hard coat film (2) (cured resin layer / TAC film) / adhesive layer (1) / polarizing plate (protective film (1) / first adhesive layer / polarizing film / second adhesive layer / protective film (2)) / adhesive layer (2) / retardation film (1) (photoalignment film / cured product layer (1)) / cured product layer of active energy ray curable composition (1) / retardation film (2) (cured product layer (2) / vertical alignment film) / adhesive layer (3) / separator film. The peeling force when peeling off the clear hard coat film (2) in the optical laminate of Example 3 from the optical laminate is 1 N / 25 mm or more.
[0161] <Example 4> A sample was obtained in the same manner as in Example 2, except that the clear hard coat film (1) was changed to the clear hard coat film (3). The optical laminate of Example 4 is composed of clear hard coat film (3) (cured resin layer / TAC film) / adhesive layer (1) / polarizing plate (protective film (1) / first adhesive layer / polarizing film / second adhesive layer / protective film (2)) / adhesive layer (2) / retardation film (1) (photoalignment film / cured product layer (1)) / cured product layer of active energy ray curable composition (1) / retardation film (2) (cured product layer (2) / vertical alignment film) / adhesive layer (3) / separator film. The peeling force when peeling off the clear hard coat film (3) in the optical laminate of Example 4 from the optical laminate is 1 N / 25 mm or more.
[0162] <Example 5> A sample was obtained in the same manner as in Example 2, except that the clear hard coat film (1) was changed to the clear hard coat film (5). The optical laminate of Example 5 is composed of clear hard coat film (5) (cured resin layer / TAC film) / adhesive layer (1) / polarizing plate (protective film (1) / first adhesive layer / polarizing film / second adhesive layer / protective film (2)) / adhesive layer (2) / retardation film (1) (photoalignment film / cured product layer (1)) / cured product layer of active energy ray curable composition (1) / retardation film (2) (cured product layer (2) / vertical alignment film) / adhesive layer (3) / separator film. The peeling force when peeling off the clear hard coat film (5) in the optical laminate of Example 5 from the optical laminate is 1 N / 25 mm or more.
[0163] <Comparative Example 1> A sample was obtained by cutting a sample of 150 mm x 50 mm so that, without laminating a clear hard coat film, when viewed from the polarizing plate side of the separator-attached optical laminate, the optical axis of the polarizing film was 45° clockwise based on the long side, and the slow axis of the retardation film was oriented at an additional 45° clockwise to the absorption axis of the polarizing film. The optical laminate of Comparative Example 1 consisted of a polarizing plate (protective film (1) / first adhesive layer / polarizing film / second adhesive layer / protective film (2)) / adhesive layer (2) / retardation film (1) (photoalignment film / cured product layer (1)) / cured product layer of active energy ray-curable composition (1) / retardation film (2) (cured product layer (2) / vertical alignment film) / adhesive layer (3) / separator film.
[0164] <Comparative Example 2> A sample was obtained in the same manner as in Example 2, except that the clear hard coat film (1) was changed to the clear hard coat film (4). The optical laminate of Comparative Example 2 is composed of a clear hard coat film (4) (cured resin layer / acrylic film) / adhesive layer (1) / polarizing plate (protective film (1) / first adhesive layer / polarizing film / second adhesive layer / protective film (2)) / adhesive layer (2) / retardation film (1) (photoalignment film / cured product layer (1)) / cured product layer of active energy ray curable composition (1) / retardation film (2) (cured product layer (2) / vertical alignment film) / adhesive layer (3) / separator film. The peeling force required to peel the clear hard coat film (5) from the optical laminate of Comparative Example 2 is 1 N / 25 mm or more.
[0165] <Reference example> A sample was obtained in the same manner as in Comparative Example 1, except that the retardation film (1) (photoalignment film / cured layer (1)) / cured layer of active energy ray-curable composition (1) / retardation film (2) (cured layer (2) / vertical alignment film) was changed to "Pure Ace RM" (retardation film) manufactured by Teijin Limited. The optical laminate of Reference Example 1 consists of a polarizing plate (first protective film / first adhesive layer / polarizing film / second adhesive layer / second protective film) / adhesive layer (2) / PureAce RM / adhesive layer (3) / separator film.
[0166] Evaluation of optical laminates (1) Curl measurement After peeling off the separator film on the adhesive layer (3) side of each chip sample, the adhesive layer (3) was placed facing up and placed in an oven at 40°C and 60% RH for 48 hours. Immediately after removal, the chip sample was placed on a "Daiso silicone trivet" with the adhesive layer (3) in contact with the trivet. The curl heights of the four corners of the chip sample were measured with a ruler, and the maximum curl amount was recorded as the measured value. The results are shown in Tables 2 and 3.
[0167] (2) Observation of the degree of air bubbles The chip sample was placed in a 40°C, 60% RH oven for 48 hours, and immediately after removal, the separator film on the adhesive layer (3) side of the chip sample was peeled off and the chip sample was attached to an alkali-free glass plate (Corning's "Eagle-XG") using a roller. After autoclaving, the number of bubbles was counted using a magnifying glass at two points on a 50 mm side of the sample, and the sample was evaluated based on the following criteria. The results are shown in Tables 2 and 3. [Evaluation Criteria] A: Less than one bubble of 50 μm or more B: 1 to 5 bubbles of 50 μm or more C: 5 to 10 bubbles of 50 μm or more D: 10 to 15 bubbles of 50 μm or more
[0168] [Table 2]
[0169] [Table 3]
Claims
1. An optical laminate comprising a circular polarizing plate having a first polarizer protective film, a first adhesive layer, a polyvinyl alcohol-based polarizing film, a second adhesive layer, a second polarizer protective film, a first adhesive layer, and a retardation film made of a polymer of a polymerizable liquid crystal compound, which are adjacent to each other in this order, and a third protective film laminated on the first polarizer protective film side via a second adhesive layer, The thickness of the retardation film is 0.5 to 10 μm, After 48 hours have elapsed in an environment having a temperature of 40° C. and a relative humidity of 60%, the dimensional deformation rate (H1) of the first polarizer protective film, the dimensional deformation rate (H2) of the second polarizer protective film, and the dimensional deformation rate (H3) of the third protective film are expressed by the following formulas (1) and (2): -0.300 ≦ H1-H2 ≦ -0.001 (1) -0.040 ≦ (H3+H1) -H2 ≦0.100 (2) An optical laminate that satisfies the above requirements.
2. The thickness (T2) of the second polarizer protective film and the thickness (T3) of the third protective film are expressed by the following formula (3): 45 ≦ (T3 / T2)×100 ≦350 (3) The optical laminate according to claim 1 ,
3. The optical laminate according to claim 1, wherein the third protective film has a thickness of 10 to 100 μm.
4. The optical laminate according to claim 1 , further comprising a cured resin layer on the opposite side of the third protective film from the circular polarizing plate side.
5. 2. The optical laminate according to claim 1, wherein the third protective film is a triacetyl cellulose film or a polymethyl methacrylate polymer film.
6. The optical laminate according to claim 1 , wherein a peeling force when peeling the third protective film from the optical laminate is 1 N / 25 mm or more.
7. An organic electroluminescence display device comprising the optical laminate according to claim 1 .
Citation Information
Patent Citations
Laminate
JP2022096970A